Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Attitudes of special education teachers towards using technology in inclusive classrooms: a mixed-methods study - Mohamed, Ahmed Hassan Hemdan (Journal of Research in Special Educational Needs, 2018)
The purpose of this mixed-methods study was to explore special education teachers’ attitudes towards using technology in inclusive classrooms in Oman. The sample consisted of 428 special education teachers working in Omani public schools (250 teachers of students with learning disabilities (LD), 90 teachers of students with intellectual disability and 88 teachers of students with hearing impairment). Participants responded to the attitudes towards computers questionnaire. For the qualitative section of this study, three semi-structured group interviews were conducted with a group of special education teachers: 15 teachers of students with hearing impairment, 15 teachers of students with intellectual disabilities and 15 teachers of students with LD). Also, the teachers responded to a survey of educational technology which encompassed seven questions about computer technology. Results of the study indicated that the special education teachers’ attitudes towards using computers were generally positive. The most notable positive attitudes were in the following subscales: special education considerations, staff development considerations, computers use in society, and computers and quality of instruction issues. The analysis of variance results showed that experience and type of disability did not have a significant effect on teachers’ attitudes towards technology.
KerkoCite.ItemAlsoKnownAs: 10.1111/1471-3802.12411 2339240:VM328LPK 2405685:7J6H34I4
Keywords: Attitudes; hard of hearing; inclusive education; intellectual disability; learning disabilities; technology

Who’s teaching math to our most needy students? A descriptive study - Rosas, Clarissa; Campbell, Lisa (Teacher Education and Special Education, 2010)
The No Child Left Behind Act (NCLB) mandates that every classroom be staffed with a “highly qualified teacher.” Research supports that teachers’ content knowledge affects student achievement. However, the special education population continues to be taught by teachers who do not have the content area background they teach. In addition, accountability reports indicate that the special education population did not meet the adequate yearly progress in reading and mathematics as required under NCLB. The purpose of this study is to determine the mathematical background, beliefs, and perceptions of future intervention specialists. Results of this study indicate a disconnect between the participants’ beliefs and perceptions of their ability to provide math instruction and their limited mathematical background as measured by mathematical courses completed at the undergraduate level and by the Ohio Achievement Test—Practice Eighth Grade Mathematics.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1177/0888406409357537 2339240:7V955V2Q 2405685:YHKAEKGD
Keywords: math; special education; standardized tests; teacher’s perception

5 Ways EdTech Helps Students With Special Needs in the Classroom - Davis, Chris (ViewSonic Library, 2019)
EdTech helps students with special needs to engage with learning better than ever before. Find out how to implement EdTech as assistive technology.
Library Catalog: www.viewsonic.com Section: Education KerkoCite.ItemAlsoKnownAs: 2339240:L69ICGF3 2405685:SCWN8NNM SCWN8NNM

A model of distance special education support services amidst COVID-19 - Frederick, Janice; Raabe, Ginger; Rogers, Valerie; Pizzica, Jessica (Behavioural Analysis in Practice, 2020)
The COVID-19 pandemic has significantly impacted the everyday life of many individuals across the globe. The school closures across the majority of the United States have presented administrators, educators, and behavior analysts with the unprecedented task of deciding how best to teach and support our students, especially those accessing special education services. The current paper describes the steps our program took, in light of school closures, to advocate for and ultimately create and implement a model that allows special education students to access the behavior analytic educational supports they had received on campus (e.g., BCBA and paraprofessional support) in a novel and remote manner. We share details regarding the advocacy and collaboration process as well as the distance special education support model itself in hopes that similar processes and models can be implemented across geographical locations to assist special education students in accessing their educational and behavioral supports in a meaningful way throughout current and future school closures.
Publisher: Behavior Analysis in Practice KerkoCite.ItemAlsoKnownAs: 10.31234/osf.io/q362v 2405685:I96LI4KA
Keywords: Applied behavior analysis; California Department of; applied behavior analysis; california department of education; covid-19; nonpublic agency; special education

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Teachers' Attitude and Competence in the Use of Assistive Technologies in Special Needs Schools - Onivehu, Adams Ogirima; Ohawuiro, Onyiyeche Emilia; Oyeniran, Bunmi Juliana (Acta Didactica Napocensia, 2017)
This study examined teachers' attitude and competence in the use of assistive technologies in special needs schools. The descriptive survey method was employed for the study among 100 teachers who were drawn using purposive sampling technique from special needs schools in Osun State, Nigeria. Six research questions were generated while four hypotheses were tested at 0.05 level of significance. A researcher-constructed questionnaire tagged "Teachers' Attitude and Competence in the Use of Assistive Technology Questionnaire" ("TACUATQ") was used for data collection. The instrument was administered on 20 selected teachers outside the sample location through test-retest method; it yielded a reliability coefficient of 0.85 through Pearson Product Moment Correlation statistics. Data were analysed with percentage, mean and rank order, t-test and ANOVA statistical tools. The findings revealed that teachers have a positive attitude towards the use of assistive technologies. However, teachers were not competent in the use of assistive technologies. Gender and teaching experience did not influence teachers' attitude and competence in the use of assistive technologies. It was recommended among other things that teachers should be trained and re-trained on the use of assistive technology for students with speech disorders, visual impairments, hearing impairments, physical impairments and emotional and behavioural disorders.
Publisher: Babes-Bolyai University KerkoCite.ItemAlsoKnownAs: 10.24193/adn.10.4.3 2339240:FDGRYPVG 2405685:TUG39XRX
Keywords: Assistive Technology; Elementary Secondary Education; Foreign Countries; Gender Differences; Questionnaires; Special Needs Students; Special Schools; Teacher Attitudes; Teacher Competencies; Teacher Surveys; Teaching Experience

International distance learning in special education: a program evaluation of a US-Ecuador collaboration - McPherson, Rebekah (University of North Texas, 2010)
The internationalization of distance learning in special education is at a pivotal point in expansion. Even with concerted efforts through traditional means to increase the supply of special educators, shortages persist; therefore, teacher preparation programs are turning to online education. This dissertation study was a formative program evaluation of a bilingual, two-course sequence within a web-based special education master’s program offered at the University of North Texas (UNT), in Denton, Texas, and at the Universidad Casa Grande (UCG) in Guayaquil, Ecuador. The research design was based on the unfolding model of program evaluation, and it included mixed-methods of data collection. The model focused attention on (1) scientific evidence, (2) cost-benefit differential, (3) underlying values, and, (4) unintended consequences. Data came from archived documents as well as six semi-structured interviews with stakeholders and survey data from 23 student participants. The findings for the general-orientation course, Special Education Programs and Practices, revealed mixed results concerning multicultural awareness on the part of student participants. However, it seemed to have influenced their lesson design and made a difference in other areas. Some multicultural awareness concepts frequented the discussion board. The specialized course, Assistive Technology, which had more frequent communication between UNT and UCG on the discussion board, suggested larger increases in students’ multicultural awareness. With respect to both courses, the stakeholders recommended that the structure be strengthened for non-bilingual instructors and students to be able to communicate more freely.
ISBN: 978-1-124-34768-4 Publication Title: ProQuest Dissertations and Theses 3436539 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/818457302?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2339240:RU2VEJFD 2405685:37N9VRF7 2405685:PGTN56VE 2534378:3DJPRT2X 2534378:ERVGUH59 2534378:NSJ46FI4
Keywords: 0529:Special education; 0530:Teacher education; 0710:Educational technology; Curriculum Design; Data Collection; Disabilities; Distance Education; Distance learning; ERIC; Resources in Education (RIE); Ecuador; Education; Educational Technology; Educational technology; Evidence; Foreign Countries; Graduate Students; Higher Education; International collaboration; Interviews; Masters Programs; Online instruction; Online learning; Program Evaluation; Program evaluation; Research Design; Special Education; Special education; Surveys; Teacher education; Texas; Unfolding model; United States; __:import:01; __:match:final; __:matched; __:study_id:2098174; __finaldtb

Special Needs Education: Country Data 2012 (European Agency for Development in Special Needs Education, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:2R6EC87G 2405685:A7NTS6EN

Developing Interactive Multimedia Flood Prevention Education (FPE) on Disaster Risk Reduction Learning for Students with Hearing Impairment in Special School - Robiansyah, Iva Evry; Mudjito; Yuliyati; Atiqoh (2019 5th International Conference on Education and Technology (ICET), 2019)
This study aims to describe the practicality of interactive multimedia flood prevention education (FPE) in improving the understanding of flood disaster risk reduction (DRR) and describing the understanding of flood disaster management learning for students with hearing impairment. This development research used the design of media development stages according to Luther with the development of media applications based on 5 stages namely: concept, design, material collecting, assembly, testing. Data were collected from through observation and tests. The result of this development product is interactive multimedia flood prevention education (FPE) to tackle flood risk among students with hearing impairment. Based on research on the development of interactive multimedia flood prevention education (FPE) to reduce the risk of flooding for students with hearing impairment in Special School Pasuruan City, it can be concluded that the results of the questionnaire show that the students' responses were very positive in using multimedia FPE in reducing the risk of flood disasters.
0 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1109/ICET48172.2019.8987227 2339240:W2CBCAC5 2405685:8HMZKBXQ
Keywords: disaster risk reduction; flood prevention education; interactive multimedia; special school; students with hearing impairment; ⛔ No INSPIRE recid found

Interactive Apps Promote Learning of Basic Mathematics in Children With Special Educational Needs and Disabilities - Pitchford, Nicola J.; Kamchedzera, Elizabeth; Hubber, Paula J.; Chigeda, Antonie L. (Frontiers in Psychology, 2018)
Interactive apps delivered on touch-screen tablets can be effective at supporting the acquisition of basic skills in mainstream primary school children. This technology may also be beneficial for children with Special Educational Needs and Disabilities (SEND) as it can promote high levels of engagement with the learning task and an inclusive learning environment. However, few studies have measured extent of learning for SEND pupils when using interactive apps, so it has yet to be determined if this technology is effective at raising attainment for these pupils. We report the first observational study of a group of 33 pupils with SEND from two primary schools in Malawi that are implementing a new digital technology intervention which uses touch-screen tablets to deliver interactive apps designed to teach basic mathematical skills. The apps contain topics that align to the national curriculum. To assess learning gains, rate of progress (minutes per topic) for each pupil was determined by calculating the average time taken to complete a topic. Progress rate was then correlated with teacher ratings of extent of disability and independent ratings of pupil engagement with the apps. Results showed SEND pupils could interact with the apps and all pupils passed at least one topic. Average progress rate for SEND pupils was twice as long as mainstream peers. Stepwise regression revealed extent of disability significantly predicted progress rate. Further exploratory correlations revealed pupils with moderate to severe difficulties with hearing and/or language made slower progress through the apps than those with greater functionality in these two domains because the use of verbal instructions within the apps limited their capacity to learn. This original quantitative analysis demonstrates that interactive apps can raise learning standards in pupils with SEND but may have limited utility for pupils with severe difficulties. Software modifications are needed to address specific areas of difficulty preventing pupils from progressing.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2018.00262 2339240:DUN6JGMK 2339240:UQ8D45IR 2405685:7WAJ6HEZ 2405685:JSQPF627
Keywords: Interactive apps; Mathematics; Special educational needs and disabilities; primary school; tablet technology

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Publisher: Routledge _eprint: https://doi.org/10.1080/14623943.2017.1361921 KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2339240:UPNEHQVJ 2405685:8CQU3AHD
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Smart buys, great sales and special offers: cost-effective approaches to improve global learning - Lewin, Keith; Learning | 0; Learning | 0 (The Education and Development Forum (UKFIET), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4GZPTGRL 2405685:7CGSPQI6

Early reading learning for special needs students: challenges on inclusive primary school during COVID-19 pandemic - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari; Trisnani, Rischa Pramudia (Linguistics and Culture Review, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21744/lingcure.v5nS1.1489 2339240:QPIH3CL4 2405685:NWJ2HG9I
Keywords: ⛔ No INSPIRE recid found

Enhancing peer interaction: an aspect of a high-quality learning environment in Finnish early childhood special education - Syrjämäki, Marja; Sajaniemi, Nina; Suhonen, Eira; Alijoki, Alisa; Nislin, Mari (European Journal of Special Needs Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1080/08856257.2016.1240342 2339240:KX7AIXX6 2405685:UBAETY3T

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118401 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1025 ZenodoArchiveConcept: 11118400
Keywords: _r:AddedByMyEducationEvidence

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13907321 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1067 ZenodoArchiveConcept: 13907320
Keywords: _r:AddedByMyEducationEvidence

Inclusive and special education approaches in developing countries - Price, Roz (Institute of Development Studies, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7AUCVAJC 2405685:ICKQU7NT
Keywords: ⛔ No DOI found

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Salamanca Statement and Framework for Action on Special Needs Education - Spain. Ministerio de Educación y Ciencia (1994)
KerkoCite.ItemAlsoKnownAs: 2339240:W3UI2IIX 2405685:YFBR7ZT8

Assistive Technology for Special Education Students - Disability Rights Washington (Disability Rights Washington)
This publication provides a definition of assistive technology, a brief overview of basic special education requirements related to assistive technology
KerkoCite.ItemAlsoKnownAs: 2339240:8JZMP38K 2405685:8PCDCLC7
Keywords: ⛔ No INSPIRE recid found

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics: - Kiboss, Joel Kipkemboi (Journal of Educational Computing Research, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Ken...
Sage CA: Los Angeles, CA shortDOI: 10/ggdtp3 KerkoCite.ItemAlsoKnownAs: 10.2190/EC.46.1.b 10.2190/ec.46.1.b 10/ggdtp3 2339240:E2A49LQS 2339240:SRIBPMIE 2405685:TBHFERAU 2405685:Z3BJFVR2

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Publisher: IISTE KerkoCite.ItemAlsoKnownAs: 2339240:VXMFTYG8 2405685:8FZZT8ZT
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Facilitators and barriers of assistive technology and learning environment for children with special needs - Lersilp, Suchitporn; Putthinoi, Supawadee; Lersilp, Theeratorn (Occupational Therapy International, 2018)
The purpose of this research was to study the facilitators and barriers of assistive technology (AT) and the learning environment for children with special needs in special education schools in Chiang Mai, Thailand. The informants were one hundred and sixteen children with special needs, who studied in nursery to Grade 12, or with their caregivers. The instrument was a questionnaire applied by the International Classification of Functioning, Disability and Health (ICF) and examined for content validity by five specialists. The results in terms of AT showed that a majority of children with physical disability needed it for mobility and use of school buildings and those with hearing disability for communication. However, most of the children did not need to use AT for culture, recreation, or sports, while many considered it as a facilitator for education. In terms of the learning environment, most characteristics of the physical environment were facilitators for children with special needs, as were those of the social environment for all groups of such children. The results of this study were useful in providing information for AT and design of a learning environment relating to the varied characteristics of children with special needs in special education schools.
13 citations (Crossref) [2024-02-28] Publisher: Hindawi KerkoCite.ItemAlsoKnownAs: 10.1155/2018/3705946 2339240:MNJXAI5P 2405685:DGKJ8CRQ
Keywords: ⛔ No INSPIRE recid found

Facilitators and Barriers of Assistive Technology and Learning Environment for Children with Special Needs - Lersilp, Suchitporn; Putthinoi, Supawadee; Lersilp, Theeratorn; Mackenzie, Lynette (Occupational Therapy International, 2018)
The purpose of this research was to study the facilitators and barriers of assistive technology (AT) and the learning environment for children with special needs in special education schools in Chiang Mai, Thailand. The informants were one hundred and sixteen children with special needs, who studied in nursery to Grade 12, or with their caregivers. The instrument was a questionnaire applied by the International Classification of Functioning, Disability and Health (ICF) and examined for content validity by five specialists. The results in terms of AT showed that a majority of children with physical disability needed it for mobility and use of school buildings and those with hearing disability for communication. However, most of the children did not need to use AT for culture, recreation, or sports, while many considered it as a facilitator for education. In terms of the learning environment, most characteristics of the physical environment were facilitators for children with special needs, as were those of the social environment for all groups of such children. The results of this study were useful in providing information for AT and design of a learning environment relating to the varied characteristics of children with special needs in special education schools.
KerkoCite.ItemAlsoKnownAs: 10.1155/2018/3705946 2339240:IP8YALEF 2405685:RQFMF9HT

Education Ministry creates special online study platform for SHS students (2020)
The Ministry for Education has launched a special online study platform for Senior High School students. Ever since Covid-19 halted school activities the Education Ministry together with the Ghana Education Service has stepped up efforts to help...
Library Catalog: www.ghanaweb.com KerkoCite.ItemAlsoKnownAs: 2405685:BM7HEL24

Education and Disability in the Global South: New Perspectives from Africa and Asia - Singal, Nidhi; Lynch, Paul; Johansson, Shruti Taneja (Bloomsbury Publishing, 2018)
Education and Disability in the Global South brings together new and established researchers from a variety of disciplines to explore the complexities and dilemmas encountered in providing education to children and young people with disabilities in countries in South Asia and Africa. Applying a range of methodological, theoretical and conceptual frameworks across different levels of education systems, from pre-school to higher education, the contributors examine not just the barriers but also the opportunities within the educational systems, in order to make strong policy recommendations. Together, the chapters offer a comprehensive overview of a range of issues, including a nuanced appreciation of the tensions between the local and global in relation to key developments in the field, critiquing a globalized notion of inclusive education, as well as proposing new methodological advancements in taking the research agenda forward. Empirical insights are captured not just from the perspectives of educators but also through engaging with children and young people with disabilities, who are uniquely powerful in providing insights for future developments.
Google-Books-ID: get1DwAAQBAJ KerkoCite.ItemAlsoKnownAs: 2339240:DZELW96T 2405685:9MZNXBIX
Keywords: Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Special Education / General

Survey of the Use of Assistive Technology in Schools in Nigeria - Ajuwon, Paul M.; Chitiyo, George (Journal of the International Association of Special Education, 2015)
In this study, the researchers explored the state of the use of assistive technology (AT) in Nigeria through a survey of 165 special educators. The underlying structure of the respondents' perceptions, and their challenges and barriers to the use of AT, were examined. Among other findings, the largest proportion of students using AT are those with deafness or hearing impairment (53.3%), followed by those with a learning disability (40%). Training in the use of AT lags behind, with most professionals having received little or no training in the use of AT. The lack of appropriate AT devices and services in classrooms, and irregular electricity to operate available devices, were frequently cited as the biggest challenges regarding AT. Correlations between students' conditions and factors of teachers' perceptions suggested the need to make AT available for students with certain conditions, as well as the need for effective training for teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:2B5LKGDA 2405685:XS664IV7
Keywords: Access to Computers; Assistive Technology; Barriers; Computer Uses in Education; Deafness; Disabilities; Educational Technology; Energy; Faculty Development; Foreign Countries; Hearing Impairments; Learning Disabilities; Likert Scales; Special Education Teachers; Statistical Analysis; Teacher Competencies; Teacher Surveys; Technological Literacy; Training; ⛔ No DOI found

Use of Assistive Technology in Inclusive Education: Making Room for Diverse Learning Needs - Ahmad, Fouzia Khursheed (Transcience)
Technology has great potential in providing to all learners the ability to access the general education curriculum, and with effective integration of assistive technology into the regular classroom, students with special needs can have the provision
KerkoCite.ItemAlsoKnownAs: 2339240:ABVH4PHV 2405685:CX2KKPW3
Keywords: ⛔ No DOI found

Using learning profiles to inform education priorities: An editors’ overview of the Special Issue - Crouch, Luis; Kaffenberger, Michelle; Savage, Laura (International Journal of Educational Development, 2021)
This special issue explores the use of learning profiles for analysing the dynamics of low learning in low- and middle-income countries and informing priorities to address the learning crisis. The 12 papers in the special issue draw on learning data from more than 50 countries and 6 million individuals, with implications for education policy and practice. Taken together, they point to a need to steepen learning trajectories by prioritizing early mastery of foundational skills for all children. The papers show that addressing the learning crisis will not be achieved through more school grade attainment alone, nor through within-country equality across groups (such as girls and boys or rich and poor). Positive examples show that programs focused on foundational learning both improved average learning and reduced inequality. Addressing the learning crisis will require a focus on systems improvement, using foundational learning as a case in point for making the needed systems improvements to steepen learning throughout children’s time in school. Learning profiles can provide a guide for education actors aiming to improve learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102477 2339240:URQN9N62 2405685:XXLGUC8W
Keywords: Education systems; Foundational skills; Inequality; Learning crisis; Learning profiles

The Efficacy of Low Vision Devices for Students in Specialized Schools for Students who are Blind in Kathmandu Valley, Nepal - Joshi, Mahesh R.; Yamagata, Yoshitaka; Akura, Junsuke; Shakya, Suraj (Journal of Visual Impairment & Blindness, 2008)
In Nepal, children with low vision attend specialized schools for students who are totally blind and are treated as if they were totally blind. This study identified children with low vision and provided low vision devices to them. Of the 22% of the students in the school who had low vision, 78.5% benefited from the devices. Proper devices and counseling improved the quality of life of a significant number of these students.
KerkoCite.ItemAlsoKnownAs: 10.1177/0145482X0810200706 2339240:NAYABQLP 2405685:KZELTSAK

Why people use and don’t use technologies: Introduction to the special issue on assistive technologies for cognition/cognitive support technologies - Scherer, Marcia J.; Federici, Stefano (NeuroRehabilitation, 2015)
This special issue focuses on assistive technologies for cognition/cognitive support technologies as well as the ways in which individuals are assessed and trained in their use. We provide eleven diverse articles that give information on products, why they are used and not used, and best professional practices in service provision. Our goal is to highlight a broad topic that has received limited research investigation and offer an insight into how different countries and programs are promoting access to and use of assistive technologies for cognition/cognitive support technologies
Publisher: IOS Press KerkoCite.ItemAlsoKnownAs: 10.3233/NRE-151264 2339240:RXAAUBQE 2405685:AKMUZPJ4
Keywords: Assistive technology devices; Matching Person and Technology Model; abandonment; assistive technology services; brain injury; cognitive support technologies; nonuse

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Variables affecting teachers' attitudes towards inclusive education in Bangladesh - Ahmmed, Masud; Sharma, Umesh; Deppeler, Joanne (Journal of Research in Special Educational Needs, 2012)
Inclusive education is a worldwide reform strategy intended to include students with different abilities in mainstream regular schools. Evidence from previous research shows that success in implementing effective inclusive teaching practices in the school is contingent on teachers' positive attitudes towards inclusive education. This study was conducted in the context of primary education in Bangladesh aiming to examine variables influencing teachers' attitudes towards inclusion of students with disabilities in regular classrooms. Data for the study was collected from 738 teachers working in 293 government primary schools in Bangladesh. The results indicated that perceived school support for inclusive teaching practices and a range of demographic variables including previous success in teaching students with disabilities and contact with a student with a disability were associated with more positive attitudes of the teachers towards the inclusive education. The results are discussed with possible implications for educators, policy-makers and international organisations working on the implementation of inclusive education. © 2012 The Authors. Journal of Research in Special Educational Needs
KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2011.01226.x 2339240:EJGQITXV 2405685:KJHBE65X

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819139 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1045 ZenodoArchiveConcept: 12819138
Keywords: _r:AddedByMyEducationEvidence

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 2339240:9SHHNJCH 2405685:WQ7ZLZVW
Keywords: ___working_potential_duplicate

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 2339240:G6HTWKIA 2405685:5VS97KU6

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819042 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1043 ZenodoArchiveConcept: 12819041
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Summary: EdTech in Vietnam - A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12818950 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1041 ZenodoArchiveConcept: 12818949
Keywords: _r:AddedByMyEducationEvidence

Inclusive education and students without special educational needs - Ruijs, Nienke; Van der Veen, Ineke; Peetsma, Thea (Educational Research, 2010)
Background: In the debate on inclusive education, students without special educational needs (SEN) are an important topic. However, there is a lot unknown about differences between these typical students in inclusive and non-inclusive classes. For example, the neutral results that are often found in earlier research could be caused by positive effects for some students, and negative effects for others.Purpose: This study investigated whether there is a relation between inclusive education and the academic achievement and socio-emotional functioning of typical students, and, more importantly, whether inclusive education affects the achievement and socio-emotional functioning of more and less intelligent typical students differently. Furthermore, we investigated whether differences occur by type of SEN of the included students. Here, we made a distinction between students with behavioural, cognitive and other problems.Sample: A representative sample of 27,745 students without SEN in Dutch primary education from a large cohort study in the Netherlands was used.Design and methods: Language and arithmetic tests were used to assess academic achievement. For socio-emotional functioning, both teacher and student questionnaires were used. A non-verbal IQ test was used to assess student intelligence. Based on the number of students with diagnosed SEN, the students without SEN were divided into several groups: typical students with no, a few and more than a few students with (certain types of) SEN in their class. Multi-level regression analyses were used to compare these groups.Results: For academic achievement, no differences were found between students without SEN in inclusive and non-inclusive classes. In this, we found no differences between intelligent and less intelligent typical students. For socio-emotional functioning, some differences were found, but the practical importance of these differences is unclear, since the effect sizes were small. The functioning of typical students does not meaningfully differ by type of SEN of the included students.Conclusions: The findings of this study are interesting in the light of the ongoing inclusion debate. Arguments against inclusive education often concern an assumed adverse effect on typical students. As in this study, hardly any differences were found between typical students in inclusive and non-inclusive primary school classes, this research strengthens the scientific evidence in support of inclusive education.
51 citations (Crossref) [2024-04-17] KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2010.524749 2339240:SSS5GMEL 2405685:GTTYFAFH
Keywords: ⛔ No INSPIRE recid found

Summary: EdTech in Timor-Leste - A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817786 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1040 ZenodoArchiveConcept: 12817785
Keywords: _r:AddedByMyEducationEvidence

Preparation of teachers for inclusive education in Lebanon - European Agency for Special Needs and Inclusive Education
KerkoCite.ItemAlsoKnownAs: 2339240:HJPEFLLV 2405685:WAJ4JCBD

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Technology in Disability-Inclusive Education - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for Special Educational Needs (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:WISL429K 2405685:U9RHMCM3
Keywords: ⛔ No INSPIRE recid found

Educational technology for learners with disabilities in primary school settings in low- and middle-income countries: a systematic literature review - Lynch, Paul; Singal, Nidhi; Francis, Gill Althia (Educational Review, 2022)
Educational Technology (EdTech) plays a significant role in enabling learners with disabilities to access learning at school and reduce educational and social exclusion. It also enables them to enjoy the benefits of a full school curriculum and to participate in activities in different educational arrangements. The purpose of this review was to address the existing evidence of how EdTech is being used to support learners with disabilities in order to inform future research and policymaking. It sought to contribute to an evidence base of ways to reduce barriers to learning drawing on a systematic methodology to gather evidence pertaining to access to EdTech for primary school learners with disabilities aged 6–12 years. After a thorough examination of the literature, the final sample comprised 51 published articles (43 peer-review and 8 conference papers). The review revealed examples of positive outcomes of EdTech interventions being used, particularly in special schools; however, the evidence of their efficacy is weak. The use of EdTech for learners with disabilities in low- and middle-income countries requires further, robust and long-term research that considers the involvement of learners, pedagogy and curriculum design in order to understand its impact on improving educational experiences of children with disabilities.
Publisher: Routledge _eprint: https://doi.org/10.1080/00131911.2022.2035685 KerkoCite.ItemAlsoKnownAs: 10.1080/00131911.2022.2035685 2405685:CB7LMISX 2405685:EM4VG98Q
Keywords: Educational technology; assistive technology; disability; inclusive education; low- and middle-income countries; primary education

Pakistan Social & Living Standards Measurement Survey 2018–19 - Government of Pakistan. Pakistan Bureau of Statistics, Government of Pakistan; Ministry of Planning Development & Special Initiatives (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:BD7K9LQT
Keywords: auto_merged

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10599846 ZenodoArchiveConcept: 10599845 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1004 2339240:VBH94XQQ 2405685:DJRV7KZW
Keywords: _r:AddedByMyEducationEvidence

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 ZenodoArchiveConcept: 10893091
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

An animated dictionary for hearing-impaired students in Thailand - Wicha, Santichai; Sharp, Bernadette; Sureephong, Pradorn; Chakpitak, Nopasit; Atkins, Anthony (Journal of Research in Special Educational Needs, 2012)
As English increasingly becomes the international language, many ministerial and educational organisations have identified the need to improve the competence of Thai students in speaking English. While there is significant research devoted to developing software tools to support the teaching of English as a second language, they are mostly concerned with adult learners. This project focuses on addressing the need to improve the teaching of English as a second language to primary school children with hearing impairments. This paper presents the development of an educational software tool referred to as the Total Communication with Animation Dictionary (TCAD), which supports learners in the acquisition and retention of new English lexical knowledge and is based on the theoretical approaches of Total Communication and situated learning. A series of experiments was undertaken to evaluate the effectiveness of the TCAD in improving vocabulary acquisition and retention. Early results are promising with increased learner engagement and performance compared with traditional approaches.
_eprint: https://nasenjournals.onlinelibrary.wiley.com/doi/pdf/10.1111/j.1471-3802.2012.01239.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2012.01239.x 2339240:26Y8P2ER 2405685:SY4KMK35
Keywords: Hearing-impaired students; language acquisition; total communication with 3D animation

An animated dictionary for hearing-impaired students in Thailand - Wicha, Santichai; Sharp, Bernadette; Sureephong, Pradorn; Chakpitak, Nopasit; Atkins, Anthony (Journal of Research in Special Educational Needs, 2012)
As English increasingly becomes the international language, many ministerial and educational organisations have identified the need to improve the competence of Thai students in speaking English. While there is significant research devoted to developing software tools to support the teaching of English as a second language, they are mostly concerned with adult learners. This project focuses on addressing the need to improve the teaching of English as a second language to primary school children with hearing impairments. This paper presents the development of an educational software tool referred to as the Total Communication with Animation Dictionary (TCAD), which supports learners in the acquisition and retention of new English lexical knowledge and is based on the theoretical approaches of Total Communication and situated learning. A series of experiments was undertaken to evaluate the effectiveness of the TCAD in improving vocabulary acquisition and retention. Early results are promising with increased learner engagement and performance compared with traditional approaches.
4 citations (Crossref) [2024-02-28] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1471-3802.2012.01239.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-3802.2012.01239.x 2339240:3MKR4PR5 2405685:8227VXM4
Keywords: Hearing-impaired students; language acquisition; total communication with 3D animation; ⛔ No INSPIRE recid found

Kenya Institute of Special Education (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FH3RYNEC

Sim Only Talk Deals| Vodacom Specials - Vodacom South Africa
KerkoCite.ItemAlsoKnownAs: 2405685:BPA3L5EQ

Kenya Disabiliy Resource | Special Educational Needs - Kenya Disability Resource
KerkoCite.ItemAlsoKnownAs: 2339240:NAJQUTP3 2405685:GWT2K9F7

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Revised Special Needs and Inclusive Education Policy - Ministry of Education (Republic of Rwanda, 2018)
EdTechHub.ItemAlsoKnownAs: 2405685:FIC7SLRH

Special Education and Deaf Children in Pakistan - Akram, Bushra; Bashir, Rukhsana (Journal of Elementary Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:9TKMBGYE 2405685:NQQMGAXE
Keywords: ⛔ No DOI found

Effectiveness of implementation of special education curriculum in face-to-face learning during the Covid-19 pandemic for children with special needs - Noor, Moch; Sugiantiningsih, Anak Agung Putu (International Journal of Social Science Research and Review, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:SEFWN4FY 2405685:MHJIGDIU
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Special edition for the African Union Year of Education 2024 - Education Finance Watch (World Bank, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:3TYCM4XL 2405685:UN5NA8XU

Models, Theories, and Frameworks: Contributions to Understanding Special Education Technology - Edyburn, Dave L
KerkoCite.ItemAlsoKnownAs: 2339240:LWBXF3SV 2405685:C4A8SN7L
Keywords: ⛔ No DOI found

Critical issues in advancing the special education technology evidence base - Edyburn, Dave L. (Exceptional Children, 2013)
Publisher: SAGE Publications Sage CA: Los Angeles, CA KerkoCite.ItemAlsoKnownAs: 10.1177/001440291308000107 2339240:CEK85TUR 2405685:CZ25UJQH

Special education teachers’ perceptions toward online learning during the Covid-19 pandemic - Yunita, Vania Martha; Sunardi, Sunardi; Kristiyanto, Agus (JPI (Jurnal Pendidikan Indonesia), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WGMWMERT 2405685:3RZ2MMSM
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

The use of technology in hybrid learning for student with special needs - Sarwendah, Ade Putri; Azizah, Nur; Mumpuniarti, Mumpuniarti (Journal of Education and Learning (EduLearn), 2023)
KerkoCite.ItemAlsoKnownAs: 10.11591/edulearn.v17i2.20810 2339240:B5GU9HBR 2405685:T2X4XT4J
Keywords: ⛔ No INSPIRE recid found

Report of the Special Rapporteur on extreme poverty and human rights - Alston, Philip (United Nations General Assembly, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:7DQX9NKE 2405685:M7L4IXDW

The use of technology in hybrid learning for student with special needs - Sarwendah, Ade Putri; Azizah, Nur; Mumpuniarti, Mumpuniarti (Journal of Education and Learning (EduLearn), 2023)
KerkoCite.ItemAlsoKnownAs: 10.11591/edulearn.v17i2.20810 2339240:B5GU9HBR 2405685:T2X4XT4J
Keywords: ⛔ No INSPIRE recid found

Assistive Technologies for Children with Disabilities in Inclusive and Special Schools in Indonesia - Hata, Anna; Wang, Han; Yuwono, Joko; Nomura, Shinsaku (The World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1596/40387 2339240:VSXIUHXY 2405685:PQZH5HEB
Keywords: Enhancing the quality of education for children with disabilities; including through the use of assistive technology; accepted; study addresses this knowledge gap; focusing on the Indonesian context; world bank; ⛔ No INSPIRE recid found

Parents’ satisfaction with online education for learners with special needs at the elementary level - Manguilimotan, Ramil P.; Cabalda, Jacob A.; Arnado, Anna Mie M.; Padillo, Gengen G.; Espina, Raymond C.; Capuno, Reylan G. (Cypriot Journal of Educational Sciences, 2022)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 10.18844/cjes.v17i4.7106 2339240:YA5UHSEA 2405685:SGI2VUJ6
Keywords: SEND; philipines; EdTech; accepted; publisher: Cypriot Journal of Educational Sciences; ⛔ No INSPIRE recid found

Mobile learning technology based on iOS devices to support students with special education needs - Fernández-López, Álvaro; Rodríguez-Fórtiz, María José; Rodríguez-Almendros, María Luisa; Martínez-Segura, María José (Computers & Education, 2013)
00026 shortDOI: 10/f4hnzg KerkoCite.ItemAlsoKnownAs: 10/f4hnzg 2129771:BFWDTZ88 2405685:VQRYXHV3

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Why do we care about evidence synthesis? An introduction to the special issue on systematic reviews - White, Howard; Waddington, Hugh (Journal of Development Effectiveness, 2012)
Systematic reviews are currently in high demand in international development. At least 100 new reviews are ongoing or already completed on a range of topics across the board in international development, many of which were commissioned by policy-making agencies. These new reviews need to be based on answerable questions, using methods of analysis and reporting which are appropriate for social and economic development programmes and relevant to users. This introductory paper lays out why we believe systematic reviews should be an important component of evidence-informed development policy and practice. It concludes by introducing the papers collected in this issue, which aim to demonstrate how reviews can be made to live up to the promises generated around them.
shortDOI: 10/gf3t4g KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2012.711343 10/gf3t4g 2339240:9ZS4VDFU 2405685:REZFBZQW
Keywords: -FullBiblioUHMLgen; -GeneralCitations; 3ie; CLL:en; Reviewed; impact evaluation; publicImportV1; systematic reviews

The contribution of ICTs to the delivery of special educational needs in Ghana: practices and potent - Nkansah, Godfred Bonnah; Unwin, Tim (Information Technology for Development, 2010)
KerkoCite.ItemAlsoKnownAs: 10.1080/02681102.2010.497273 2339240:6W2XSNXE 2405685:GP3VLXGC

The Issues and Challenges of Using Multimedia at a District Level, Specialized Girls’ College in Bangladesh - Sarowardy, Muhammad Hasan; Halder, Deb Proshad (Creative Education, 2019)
The use of multimedia in imparting education has inevitably been trendy owing to its multifold benefits which have been established and reinvestigated as inseparable teaching aid and tool in teaching-learning process. But This technological assisting component cannot be accorded in many of the institutions of Bangladesh due to several internal as well as external factors. This paper aims to highlight the emerging factors that beset in the institution of Bangladesh. This institutional study on the issues and challenges of using of multimedia in a district (urban area) level girls’ college projects a thorough realization of the difficulties what this types of attributive colleges face in Bangladesh. The resource constraint, the lack of motivation of the teachers, the lack of expert human resource, the insufficient digital tools and lack of multimedia-enabled class environment are found to be barriers and some guiding directives are also imposed in this paper that emerges through the interviews of the teachers and the Vice principal. Thus, the paper, in a miniature effort, tries to lay out the challenges the college of Bangladesh faces and highlight some remedial ways to cope up the challenges.
KerkoCite.ItemAlsoKnownAs: 10/gj37jg 2339240:M5B3GAH9 2405685:LDBLDTX5

Special Needs Education (SNE) in Kenyan public primary schools: exploring government policy and teachers’ understandings - Mwangi, Lucy (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:UI9VSGAF 2405685:Y7LJH3SM 4656463:T688XI8F 4820577:YUAA6DRP
Keywords: ⛔ No DOI found

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=126003617&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2405685:BC5IPJP7 2534378:8GYBJJ8Z 2534378:R2HCJDDM
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

The effect of distance learning on learning outcomes of children with special needs in inclusive schools in the new normal - Sholikhati, Nur Indah; Prayogo, Muhaimi Mughni; Santoso, Joko (Indonesian Journal of Disability Studies, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21776/ub.ijds.2021.008.01.11 2339240:8RMCQ44M 2405685:NFGHFAVD
Keywords: ⛔ No INSPIRE recid found

Innovative Strategies for Accelerated Human Resources Development in South Asia:: Information and Communication Technology for Education—Special Focus on Bangladesh, Nepal, and Sri Lanka - Asian Development Bank (Asian Development Bank, 2017)
Edition: 0 ISBN: 9789292610333 9789292610326 shortDOI: 10/ghgnfh KerkoCite.ItemAlsoKnownAs: 10.22617/TCS179080 10/ghgnfh 2339240:DC9GXZHD 2339240:H8XPPDHF 2405685:9CV4C8ZT 2405685:CIIMK9AK
Keywords: Systems Framework

Innovative strategies for accelerated human resource development in South Asia: Information and communication technology for education - Special focus on Bangladesh, Nepal, and Sri Lanka - ADB (Asian Development Bank, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:XPQH26KA 2405685:ZT5HV4GA

Harnessing EdTech for Neurodivergent Learners in LMICs - Aida, Layachi; Daniel, Plaut (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15737188 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1124 ZenodoArchiveConcept: 15737187
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

The use of computer-assisted instruction to improve the reading comprehension of students with learning disabilities: an evaluation of the evidence base according to the What Works Clearinghouse standards - Kim, Min Kyung; McKenna, John William; Park, Yujeong (Remedial and Special Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1177/0741932517693396 2339240:M673GYW8 2405685:PC4NHG5G

Inclusive considerations for optimal online learning in times of disasters and crises - Thompson, Kim M; Copeland, Clayton (Information and Learning Science, 2020)
Purpose: Special submission format guidelines indicate to insert placeholder and upload full abstract. Design/methodology/approach: Special submission format guidelines indicate to insert placeholder and upload full abstract. Findings: Special submission format guidelines indicate to insert placeholder and upload full abstract. Research limitations/implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Practical implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Social implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Originality/value: Special submission format guidelines indicate to insert placeholder and upload full abstract.
KerkoCite.ItemAlsoKnownAs: 10.1108/ILS-04-2020-0083 2405685:348CQHBQ
Keywords: Course design; Diversity; Equity; Evidence-based practice; Inclusion; Inclusive pedagogy; Learning environment; Universal design for learning; pedagogy

Using Information Communication Technologies (ICT) to Implement Universal Design for Learning (UDL) - Banes, David; Hayes, Anne; Kurz, Christopher; Kulshalnagar, Raja (University Research Co., LLC, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QM93JBAC 2405685:QDLCLTE4

The DAISY Consortium Home Page (The DAISY Consortium)
Global Reach DAISY is an international non-profit membership organization working with over 150 partners all around the world to improve access to reading for people with print disabilities Join Us… Shaping the Technology of Tomorrow At DAISY we work closely…Continue reading...
Library Catalog: daisy.org KerkoCite.ItemAlsoKnownAs: 2339240:MWJG7Y2R 2405685:MP4KZ64K MP4KZ64K

Support for children and young people with vision impairment in educational settings (Welsh Government, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BVB4T4PT 2405685:PE87BSH7

UDL: The UDL Guidelines (The UDL Guidelines)
KerkoCite.ItemAlsoKnownAs: 2339240:NTMEHEW8 2405685:8SAQYMWK 8SAQYMWK

What works? The case of inclusive education | Unesco IIEP Learning Portal - Singal, Nidhi (2018)
The Sustainable Development Goals with their commitment to ensuring all young people will have access to good quality primary and lower secondary education by 2030 have spearheaded an increased focus on children with disabilities. The SDGs explicit mention of persons with disabilities, across education and other goals have resulted in intense discussions on how to make these commitments a reality.
Library Catalog: learningportal.iiep.unesco.org KerkoCite.ItemAlsoKnownAs: 2339240:FHDY4ZTC 2405685:IJ7WBNAN IJ7WBNAN

Making Schools Inclusive: How change can happen (Save the Children UK, 2008)
KerkoCite.ItemAlsoKnownAs: 2339240:LDSPRXL5 2405685:UE78R5FZ

Assistive technology in developing countries: national and international responsibilities to implement the Convention on the Rights of Persons with Disabilities - Borg, Johan; Lindström, Anna; Larsson, Stig (The Lancet, 2009)
In developing countries, disability is often associated with poverty caused by reduced participation in education, work, and community life.1–4 Education and employment contributes to reduction of poverty, improvement of health, and increased participation in society.2,5,6 According to findings from studies in high-income countries, assistive technology can have a positive socioeconomic effect on the lives of people with disabilities by improving access to education and increasing achievement.7,8 The use of assistive technology is a successful strategy to help participation in work,9,10 and maintenance of health.
Publisher: Elsevier shortDOI: 10/cfn5gp KerkoCite.ItemAlsoKnownAs: 10.1016/S0140-6736(09)61872-9 10/cfn5gp 2339240:W45H7KRY 2405685:YQJM4J5B

Research - Edtech Solutions | All Children Reading (All Children Reading: A Grand Challenge for Development)
Explore ACR GCD’s in-depth research on the impact of edtech solutions on improving reading outcomes for children in low-resource contexts.
Library Catalog: allchildrenreading.org KerkoCite.ItemAlsoKnownAs: 2339240:MSWHDAV5 2405685:YPX7JRAA YPX7JRAA

Global perspectives on assistive technology: Proceedings of the GReAT Consultation 2019, Volume B - Day 2 (World Health Organization, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4KTX7RSQ 2405685:3DN8XRDU

Effective Use of Assistive Technologies for Inclusive Education in Developing Countries: Issues and challenges from two case studies - Grönlund, Åke; Lim, Nena; Larsson, Hannu (International Journal of Education and Development using ICT, 2010)
Developing countries face many obstacles in the process of implementing inclusive education (IE). Effective use of assistive technologies (AT) can help governments in developing countries achieve inclusive education by helping children with disabilities in schools. Despite the importance and positive impact of AT, prior research on the use of AT in inclusive education especially in developing countries is limited. To fill the research gap in this area, this paper investigates the research question of, How can AT be effectively used for IE in developing countries? To address this question,...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:MQSJ66AT 2405685:AYQJEEVW
Keywords: ⛔ No DOI found

FAQs -
Frequently Asked Questions: Questions You Have About Inclusive Education But Didn’t Know Whom To Ask Inclusion International is often asked what we mean by “inclusive education”. Here are the most common questions from our members together with our responses. The responses are based on the …
Library Catalog: inclusion-international.org KerkoCite.ItemAlsoKnownAs: 2339240:J8AA3DPC 2405685:Q9K2UYF2 Q9K2UYF2

Equitable Access to Education for Children with Disabilities - Mishra, Anant (EdTechReview)
Assistive Technology (AT) broadly categorizes the physical tools that support children with disabilities. Assistive Technology devices range..
Library Catalog: edtechreview.in KerkoCite.ItemAlsoKnownAs: 2339240:DYSTI26U 2405685:AUNZ7SZ5 AUNZ7SZ5

Inclusive Education Where there are Few Resources - Stubbs, Sue (The Atlas Alliance, 2008)
KerkoCite.ItemAlsoKnownAs: 2339240:KTZ6U4JX 2405685:UNKUFT5B

Education for children with disabilities - improving access and quality - Mattingly, Jacqui; McInerney, Laura (Department for International Development)
KerkoCite.ItemAlsoKnownAs: 2339240:3N3CDVRA 2405685:U3X8DZJI

GEM Report summary on disabilities in education (UNESCO, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:EZR4PD6B 2405685:X2YJQT9S

Disability Inclusive Education Toolkit | Education Links
This toolkit provides guidance and resources for integrating disability into the USAID Program Cycle.
Library Catalog: www.edu-links.org KerkoCite.ItemAlsoKnownAs: 2339240:6T4ATBJJ 2405685:X4CI3I9Q X4CI3I9Q

75 Digital Tools and Apps Teachers Can Use to Support Formative Assessment in the Classroom (Teach. Learn. Grow., 2019)
We’ve compiled an extensive list of 75 digital tools, apps, and platforms that can help teachers use formative assessment to elicit evidence of student learning. #education #teachers
Library Catalog: www.nwea.org Section: Formative Assessment KerkoCite.ItemAlsoKnownAs: 2339240:H4U5K8J7 2405685:WU8SHHQ8 WU8SHHQ8

Assistive Technology in the African Region: Results of an Online Rapid Assistive Technology Capacity Survey (World Health Organization Regional Office for Africa)
KerkoCite.ItemAlsoKnownAs: 2339240:GH5UISR6 2405685:8WSZWRMX

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.07.002 2339240:MXTDK768 2405685:K9AQNHDY
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Cambodia - A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Cambodia. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817714 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1038 ZenodoArchiveConcept: 12817713
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Lao People's Democratic Republic - A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Lao People's Democratic Republic. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817771 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1039 ZenodoArchiveConcept: 12817770
Keywords: _r:AddedByMyEducationEvidence

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Education and Disability in the Global South: new perspectives from Africa and Asia. London: Bloomsbury Publishing. - Singal, Nidhi; Lynch, P; Johansson, S. T (British Journal of Special Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1111/1467-8578.12292 2339240:EVTHNM88 2405685:3M6AJUNM

Universal Design for Learning to Help All Children Read: Promoting Literacy for Learners with Disabilities - Hayes, Anne; Turnbull, Ann; Moran, Norma (USAID, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:BQZXP46T 2405685:QAQ8FR9B

Participatory design of DIY digital assistive technology in Western Kenya | Proceedings of the Second African Conference for Human Computer Interaction: Thriving Communities - Hamidi, Foad; Mbullo, Patrick; Hynie, Michaela; McGrath, Susan; Baljko, Melanie
shortDOI: 10/ggqt9n KerkoCite.ItemAlsoKnownAs: 10.1145/3283458.3283478 10/ggqt9n 2339240:XX4Z4ZQT 2405685:W5PKAAH6

EdTech in Vietnam: A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. This report was originally written in March 2024. It is based primarily on desk research, with quality assurance provided by country experts at Southeast Asian Ministers of Education Organization (SEAMEO) centres. Keywords: out-of-school children and youth; digital education; Southeast Asia; girls’ education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11445854 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1031 ZenodoArchiveConcept: 11445853
Keywords: _r:AddedByMyEducationEvidence

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10616734 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1008 ZenodoArchiveConcept: 10616733
Keywords: _r:AddedByMyEducationEvidence

Towards a Disability Inclusive Education - Sæbønes, Ann-Marit; Bieler, Rosangela Berman; Baboo, Nafisa; Banham, Louise; Singal, Nidhi; Howgego, Catherine; McClain-Nhlapo, Charlotte Vuyiswa; Riis-Hansen, Trine Cecilie; Dansie, Grant Angus (Oslo Summit on Education for Development, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:JPKX5XBG 2339240:SSMZBC9V 2405685:3AIMPPZI 2405685:LDMG6PB8
Keywords: ___working_potential_duplicate

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence

Innovative Research Methodologies: Participatory Ethnographic Evaluation Research (PEER). - Oyinloye, Bukola
This podcast is the third in a series commissioned by the Research Methodology in Education Special Interest Group to showcase the variety of methodologies and methods being undertaken by...
10 May 2023 KerkoCite.ItemAlsoKnownAs: 2339240:W5CT7SK5 2405685:7ZIAGBUC

Inclusive Quality Education for Children with Disabilities - Singal, Nidhi; Ware, Hannah; Bhutani, Sweta Khanna (World Innovation Summit for Education & University of Cambridge, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:4ZA5WMI7 2339240:VS2APB8E 2339240:WALVDQHQ 2405685:B7XYHF4V 2405685:G784RVFY 2405685:UHVMVWIX

Education of children with disabilities in India and Pakistan: Critical analysis of developments in the last 15 years - Singal, Nidhi (PROSPECTS, 2016)
This article presents an analysis of key developments in educational policies and strategies, since 2000, in relation to the education of children with disabilities in India and Pakistan. It responds to a set of specific questions focused on factors that have shaped the increased emphasis on education of children with disabilities, how national policies and programmes respond to their needs, and their current educational status. The article draws on analysis of official policies, various programme documents, and empirical research evidence. It concludes by reflecting on the two main foci for future work in relation to the education of children with disabilities.
shortDOI: 10/gftstb KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-016-9383-4 10/gftstb 2339240:UC62U9Y7 2405685:V4R3ZU7R

COVID-19 and girls' education: A tale of two futures
Julia Gillard will join UK Special Envoy for Girls' Education Baroness Sugg and youth from around the world for a dialogue on how COVID-19 is affecting girls' education from around the world
Library Catalog: www.globalpartnership.org KerkoCite.ItemAlsoKnownAs: 2405685:4BR5DMXH

Educational outcomes and research from 1:1 computing settings - Bebell, D.; O'Dwyer, L. M. (Journal of Technology, Learning, and Assessment, 2010)
Despite the growing interest in 1:1 computing initiatives, relatively little empirical research has focused on the outcomes of these investments. The current special edition of the Journal of Technology and Assessment presents four empirical studies of K-12 1:1 computing programs and one review of key themes in the conversation about 1:1 computing among advocates and critics. In this introduction to our 1:1 special edition, we synthesize across the studies and discuss the emergent themes. Looking specifically across these studies, we summarize evidence that participation in the 1:1 programs was associated with increased student and teacher technology use, increased student engagement and interest level, and modest increases in student achievement.
KerkoCite.ItemAlsoKnownAs: 2129771:TV2JLSG4 2405685:3HZ7QNKB
Keywords: ⛔ No DOI found

Parents’ perceptions of secondary school students’ motivation and well‐being before and during the COVID‐19 lockdown: the moderating role of student characteristics - Hornstra, Lisette; van den Bergh, Linda; Denissen, Jaap J. A.; Diepstraten, Isabelle; Bakx, Anouke (Journal of Research in Special Educational Needs, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1111/1471-3802.12551 2339240:DSJW9SL5 2405685:Y4N6RW4S

Inservice Training of Primary Teachers through Interactive Video Technology: An Indian Experience - Raina, V. K.; Maheshwari, A. N. (International Review of Education, 1998)
Discusses India's Special Orientation Programme for Primary School Teachers (SOPT), a new technology used to train large numbers of teachers so that the losses in transmission inherent in the "cascade model" are avoided. Responses from teachers and trainers show there is considerable potential for the exploitation of this technology. Contains 20 references. (VWC)
shortDOI: 10/dm4mmz KerkoCite.ItemAlsoKnownAs: 10.1023/A:1003103813259 10/dm4mmz 2405685:6TAN2XRY

#CostingEquity: The case for disability-responsive education financing - Myers, Juliette; Pinnock, Helen; Baboo, Nafisa; Lewis, Ingrid (International Disability and Development Consortium, 2018)
The #CostingEquity research project investigated the benefits of financing disability-inclusive education, the current state of education financing with regard to inclusion, and what needs to change in order for education financing to effectively support the realisation of SDG 4. The #CostingEquity research report addresses three broad questions: • How do international donors and domestic governments currently fund disability-inclusive education? • What are the gaps and challenges in financing disability-inclusive education? • What needs to change to increase quality, equitable financing for learners with disabilities? The report aims to contribute to a better understanding of the issues related to equitable financing for education for learners with disabilities. It considers additional marginalising factors such as gender, socio-economic status, social circumstances and urban/rural location. It offers key arguments for civil society activists, donors and government advisors to make the case for building and strengthening inclusive education systems. Detailed case studies provide useful examples of financing gaps, challenges and promising practice from developing country contexts, major education donors, and new and emerging philanthropic donor foundations. The focus of case studies and examples is on low and lower-middle income countries and were chosen to reflect a broad range of regions and countries.The report concludes with a series of recommendations for domestic and external financing approaches.
KerkoCite.ItemAlsoKnownAs: 2339240:3XWFXVAP 2339240:DU3DQXWC 2405685:9WX2Z28W 2405685:EQP34VAJ

Convention on the Rights of Persons with Disabilities - United Nations (United Nations Human Rights Office of the High Commissioner, 2006)
Convention Ratifications/Accessions: 182 Signatories*: 164 Optional Protocol Ratifications/Accessions: 96 Signatories*: 94 (* Signatories include countries or regional integration organizations that have signed the Convention and its Optional Protocol) 10th Anniversary of the adoption of CRPD: 2006 to 2016 Infographic on the CRPD and the COSP (prepared October 2016: (Word, PDF) Status of Ratifications to the CRPD (prepared May 2016) (JPG, […]
KerkoCite.ItemAlsoKnownAs: 2339240:5IDS3FHB 2339240:9N929PHG 2339240:PQDH9LW2 2405685:3FCY2QN4 2405685:C5PEP2G4 2405685:ZCMN87NZ
Keywords: ⛔ No INSPIRE recid found

SWIFT-Active Screener (Sciome)
SWIFT-Active Screener is a web-based, collaborative systematic review software application. Active Screener was designed to be easy-to-use, incorporating a simple, but powerful, graphical user interface with rich project status updates. What makes Active Screener special, however, is its behind-the-scenes application of state-of-the-art statistical models designed to save screeners time and effort by automatically prioritizing articles […]
KerkoCite.ItemAlsoKnownAs: 2405685:SRZDALS6 2486141:JSNIAJDR

A digital accessibility and inclusive design-based e-module in Higher Education: Does it work in a classroom with a deaf student? - Musayaroh, Siti; Asmiati, Neti; Utami, Yuni Tanjung; Mulia, Dedi; Sidik, Sistriadini Alamsyah; Febri, Reza; Abadi, Toni Yudha Pratama; Maslahah, Sayidatul; Pramudyo, Anggoro Suryo (ASEAN Journal of Community and Special Needs Education, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:9P7P2HPK 2405685:LD8V7CAU
Keywords: accepted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Inclusive early childhood education in Nigeria: the journey so far - Salami, Ishola Akindele (The Journal of International Association of Special Education, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:I8MLFP73 2405685:FVLMEIML
Keywords: ⛔ No DOI found

Digital Africa: Technological Transformation for Jobs - Begazo, Tania; Blimpo, Moussa P.; Dutz, Mark (World Bank Group, 2023)
Digital Africa, Technological Transformation for Jobs examines pathways to produce and promote the expanded use of affordable and attractive digital technologies (DTs) that are appropriate for Sub-Saharan Africa’s growing workforce and facilitate continued learning through use. DTs are defined broadly to include digital and data infrastructure, broadband internet, smart phones, tablets, and computers. They also include specialized management upgrading, worker training, and training in procurement, marketing, logistics, financing, and insurance.
KerkoCite.ItemAlsoKnownAs: 2339240:HSECCCXQ 2405685:CE2YV4CW
Keywords: ⛔ No INSPIRE recid found

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.
KerkoCite.ItemAlsoKnownAs: 10.14507/epaa.25.3240 2339240:4M24F399 2405685:RNRQL9Z2
Keywords: Change in universities

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
ZenodoArchiveID: 4706019 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706019 2339240:D85SY35R 2405685:SMLIMS2X
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Appraising research on personalized learning: definitions, theoretical alignment, advancements, and future directions - Walkington, Candace; Bernacki, Matthew L. (Journal of Research on Technology in Education, 2020)
This article introduces a special issue comprising research on efforts to personalize learning in different academic subjects. We first consider the emergence of personalized learning (PL) and the myriad of definitions that describe its essential features. Thereafter, we introduce the articles in the special issue by examining their alignment to extant theories of learning, the instructional design features that personalize the learning experience based on a learner characteristic, and the relationships between PL design and outcomes achieved in an educational context. Based on observations of contemporary PL research, we identify key issues to be addressed by the field and recommendations for future researchers to undertake to advance a PL theory. Chief among issues with PL are the role of technology, the agency of the learner, and the absence of a consistent theoretical grounding to motivate PL design choices. Future directions that would advance PL include the adoption of a theory of change in PL design, a design-based research approach to refine PL initiatives, more intensive and iterative research in authentic classroom contexts, and a greater focus on student input into and ownership of the PL experience.
KerkoCite.ItemAlsoKnownAs: 10.1080/15391523.2020.1747757 2339240:DUK6NXYD 2405685:WF9TK4TD

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Mode of tele-communication and software used by children with hearing impairment - Zahra, Arjamand; Khan, Sikander Ghayas; Butt, Ayesha Kamal; Noreen, Hafsa; Saeed, Muhammad Imtiaz; Iftikhar, Nayab (Biomedical Research, 2018)
Objective: The study is being conducted to find out mode of tele-communication and software used by children with hearing impairment. Methodology: This cross-sectional study was done at special education centers and schools in Lahore and Sheikhupura. Data was collected from children with hearing impairment by using a questionnaire of 11 items about the modes of tele-communication and software used by children with hearing impairment. Sample size was 362 which was calculated by using online sample size calculator. The population includes male and female children with mild, moderate, severe and profound hearing impairment studying in special education schools of Lahore and Sheikhupura. All these children use hearing aid and have congenital bilateral hearing loss. Results: This study shows that almost 80% population of children with hearing impairment know about computer and mobile. They also have awareness about the use of computer, Facebook, e-mail etc. In addition, 40 to 50% children with hearing impairment use Skype, Facebook and e-mail as a communication tool. Conclusion: The conclusion from this study is that most of the children use computer and mobile on daily basis in schools and homes for communication. Mild to moderate hearing loss children benefit from these devices between the ages of 10 to 20 y.
Publisher: Biomedical Research KerkoCite.ItemAlsoKnownAs: 10.4066/biomedicalresearch.29-17-3494 2339240:7FCYX428 2339240:XZGUQ9KC 2405685:QFJGZFWK 2405685:U7CFTZ3Q

Promoting physical activity for children with autism spectrum disorders during Coronavirus outbreak: Benefits, strategies, and examples - Yarımkaya, Erkan; Esentürk, Oğuz Kaan (International Journal of Developmental Disabilities, 2020)
Described as a global outbreak (pandemic) by the World Health Organization, Coronavirus disease (COVID-19) raises great concern with more than 2 million infected patients worldwide. A series of measures are taken by governments worldwide to prevent the spread of the outbreak. As new cases increase, people are asked to stay at home. Active living areas such as sports centers, parks and schools are closed in most countries. In this process, staying at home for a long time makes it difficult for individuals with special needs such as Autism Spectrum Disorders (ASD) to stay physically active as well as typically developing individuals. The education process of children with ASD is disrupted, especially due to closed special education schools and rehabilitation centers. Online learning environments are often not suitable for children with ASD. It is predicted that excessive weight, obesity and sedentary life, which are high in children with ASD, may increase even more due to COVID-19. This article outlines the benefits of physical activity for children with ASD and provides strategies and examples of physical activity for children with ASD during the COVID-19 outbreak. The article is thought to be a guide for encouraging children with ASD in the home environment to physical activity.
KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2020.1756115 2405685:4SKEKBD6
Keywords: COVID-19; children with ASD; physical activity; stay at home

Optimising worked example instruction: Different ways to increase germane cognitive load - Paas, Fred; van Gog, Tamara (Learning and Instruction, 2006)
Worked examples are an effective instructional means to teach complex problem-solving skills. It has been argued that worked examples decrease extraneous load, enabling more Working Memory (WM) resources to be directed to activities that facilitate learning and transfer performance. Hence, cognitive load research has started to shift its focus towards finding instructional techniques that impose a germane cognitive load by stimulating the allocation of WM resources to such activities. This special issue provides an overview of recent experimental research on ways to further optimise the design and delivery of worked examples in order to foster learning and transfer.
shortDOI: 10/bg2wtc KerkoCite.ItemAlsoKnownAs: 10.1016/j.learninstruc.2006.02.004 10/bg2wtc 2405685:GQ7VHTE3

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Problems of drop-out students in Indian slum - Siddiqui, Tarannum (International Education and Research Journal, 2017)
The purpose of this paper is to find out the problems of drop-out students at elementary level, specially living in slum areas of India. Educational facility at elementary level and its relationship with infrastructural facilities is the main focus of this paper. Paper highlights the role of government to improve elementary education in slum areas of the country with special focus on drop-out students. Paper is mainly based on primary and secondary data/ information. Study has taken a total sample of 50 households (25 from each district) by using random sampling technique in the urban areas namely- Madiyaon slum of Lucknow in Uttar Pradesh and Dharavi slum of Mumbai in Maharashtra. Intensive interviews have been conducted to procure purpose full information. The numbers of upper primary schools were found half of the primary schools in slum areas. Acording to RTE Act no students could be stop or retained in any class of primary section. To stop drop out situation at elementary level of education, paper recommends opening more government upper primary schools in the slum areas. Due to limited sample size, the research results may lack generalisation. Therefore, researchers and research institutions are encouraged to test the proposed propositions further. Dropping out from elementary education in slum areas are an unexplored area of research which has been covered in this paper.
Number: 5 KerkoCite.ItemAlsoKnownAs: 2339240:HJCCKF7J 2405685:W2QT6EH2
Keywords: Elementary education in slum areas.; Indian slums; Problems of drop-out students; ⛔ No DOI found

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Effects of gesture-based match-to-sample instruction via virtual reality technology for Chinese students with autism spectrum disorders - Hu, Xiaoyi; Han, Zhuo Rachel (International Journal of Developmental Disabilities, 2019)
Effective strategies to address academic performance are critical to students with disabilities in inclusive settings. The purpose of this study was to investigate the effectiveness of using gesture-based instruction via Leap Motion-aided virtual reality (VR) technology to teach matching skills to school-aged students with autism spectrum disorder (ASD) in China. Three participants with ASD from general education schools participated in this study. A multiple probe design across participants was used. The results indicated that all participants acquired the target match-to-sample skills and maintained the acquired skills at a high level for up to 12 weeks. Results of this study provide important implications to special education and general education teachers working with students with ASD.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2019.1602350 KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2019.1602350 2339240:XFCC6MFH 2405685:2Q77DSNT
Keywords: China; autism spectrum disorders; computer-assisted instruction; gesture-based; match-to-sample; virtual reality technology

Gender and wealth disparities in schooling: evidence from 44 countries - Filmer, Deon (International Journal of Educational Research, 2005)
This paper uses internationally comparable household data sets (Demographic and Health Surveys) to investigate how gender and wealth interact to generate within-country inequalities in educational enrollment and attainment. The paper highlights that girls are at a great educational disadvantage in particular regions: South Asia and North, Western, and Central Africa. There are two main new findings. First, while gender gaps are large in a subset of countries, wealth gaps are large in almost all of the countries studied–and typically larger than corresponding gender gaps. Second, and of special concern, is the finding that in particular countries where there is a large female disadvantage in enrollment, wealth interacts with gender to exacerbate the gap in educational outcomes.
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijer.2006.06.012 2339240:P4L824HN 2405685:N7TD7EH3
Keywords: Comparative Analysis; Educational Attainment; Enrollment; Evidence; Females; Fiscal Capacity; Foreign Countries; Gender Differences; Outcomes of Education

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
ZenodoArchiveID: 4705912 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705912 2339240:26FUGGA3 2339240:X339ME8R 2405685:EHKCNED4 2405685:NIVS5RZF 2405685:TWMVIX77
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Using Universal Design for Learning to design standards-based lessons - Rao, Kavita; Meo, Grace (Sage Open, 2016)
The Universal Design for Learning (UDL) framework can be used to proactively design lessons that address learner variability. Using UDL guidelines, teachers can integrate flexible options and supports that ensure that standards-based lessons are accessible to a range of learners in their classrooms. This article presents a process that teachers can use as they develop standards-based lesson plans. By “unwrapping” academic standards and applying UDL during the lesson planning process, teachers can identify clear goals aligned with an academic standard and develop flexible methods, assessments, and materials that address the needs and preferences of varied learners. General educators and special educators can use this process to develop inclusive lesson plans that address all learners, with and without disabilities.
KerkoCite.ItemAlsoKnownAs: 10.1177/2158244016680688 2339240:W4M6LDLT 2405685:S42A7PKF

List of types of systems theory - Wikipedia (Wikipedia, 2021)
This list of types of systems theory gives an overview of different types of systems theory, which are mentioned in scientific book titles or articles. The following more than 40 types of systems theory are all explicitly named systems theory and represent a unique conceptual framework in a specific field of science. Systems theory has been formalized since the 1950s, and a long set of specialized systems theories and cybernetics exist. In the beginnings, general systems theory was developed by Ludwig von Bertalanffy to overcome the over-specialisation of the modern times and as a worldview using holism. The systems theories nowadays are closer to the traditional specialisation than to holism, by interdependencies and mutual division by mutually-different specialists.
Page Version ID: 998624856 KerkoCite.ItemAlsoKnownAs: 2339240:9ZNWIT4X 2405685:XFYANJMX

Guidance Note 4 Inclusion and accessible learning for people with disabilities From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684317 2339240:LKN74WQK 2405685:56QA2K9Y
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

iPad: efficacy of electronic devices to help children with autism spectrum disorder to communicate in the classroom - Sankardas, Sulata Ajit; Rajanahally, Jayashree (Support for Learning, 2017)
Children with Autism Spectrum Disorder (ASD) are known to have difficulty in social communication, with research indicating that children with ASD fail to develop functional speech (Lord and Rutter, 1994). Over the years a number of Augmented and Alternate Communication (AAC) devices have been used with children with ASD to overcome this barrier and to facilitate communication. This article examines an Indian AAC tool called AVAZ (meaning sound), which is the first of its kind in India. The project reported also looks at the effectiveness of using AVAZ and the use of iPads by children with ASD in the classroom. Additionally, the article examines the suitability of using iPads for all learners in the spectrum. Twenty children between the ages of 4 and 10 years were selected to trial the use of AVAZ. They received three sessions weekly of 45 minutes over a period of 10 weeks. The feedback of the special educators who trained the children was analysed. The findings of this small scale study indicates that the children preferred using the AVAZ app and the iPad to pen and paper. Huguenin (2004) too indicated similar reports in using Information and Communication Technology (ICT) in enhancing children's motivation to learn and communicate. The trainers felt it could be used as an educational tool, and many more educational concepts could be added. Research also suggests that ICT can be used as a tool to tutor for educational purpose (Means, 1994). The AVAZ app could be recommended to children with ASD who are included in mainstream schools. This study was conducted at Sankalp, a special school in Tamil Nadu, Chennai.
_eprint: https://nasenjournals.onlinelibrary.wiley.com/doi/pdf/10.1111/1467-9604.12160 KerkoCite.ItemAlsoKnownAs: 10.1111/1467-9604.12160 2339240:B3KGPHPK 2405685:R92QINFG
Keywords: alternate and augmented communication; autism spectrum disorder; information and communication technology; social communication

ICTs in Learning in Pakistan - Hassan, Taimoor; Sajid, Ar (International Journal of Evaluation and Research in Education (IJERE), 2012)
The paper investigates the barriers to the integration of Information and Communication Technologies (ICTs) at secondary level learning in Pakistan, with special emphasis on Punjab province. Exploring major barriers to the integration of ICTs at the school level, teacher level and student level and possible enablers to these barriers is the major focus of study. Sequential mixed method design is used. Interviews were analysed qualitatively whereas survey questionnaire were analysed quantitatively. It is observed from the findings that most of the participants have positive perceptions about integration of ICTs into their teaching and learning. Administrators and ICT coordinators revealed many barriers and possible enablers to the integration of ICTs. Many of these barriers are verified by the teachers and students. Later on however there were some barriers which were not endorsed by the teachers and students.
KerkoCite.ItemAlsoKnownAs: 10.11591/ijere.v1i2.1244 2339240:N34T78WC 2405685:5INDIDCV

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

How to teach English in India: testing the relative productivity of instruction methods within the Pratham English language education program - He, Fang; Linden, Leigh L; MacLeod, Margaret (2008)
Using a pair of randomized evaluations, we assess the relative productivity of several modes of implementing an Indian English education curriculum. Each consists of a specially designed machine or flash card based activities implemented either indirectly through a teacher training program or directly by externally supervised teaching assistants. The new methods are very effective and, on average, all implementation strategies yield gains of about 0.25-0.35 standard deviations in students’ knowledge of English. Weaker students benefit more from interventions that include teacher directed activities while stronger students benefit more from the more self-paced machine-based implementation. Compared to an externally implemented version of the curriculum, the treatments implemented through the teacher training program improved students’ math and English scores rather than just their English scores, a result that may be due to the fact that teachers implemented the interventions more efficiently.
KerkoCite.ItemAlsoKnownAs: 2339240:YK589CIH 2405685:RQYG6BYY 683578:JQU56E9F
Keywords: THEME: Curriculum and resources; ⛔ No DOI found

National Policies that Connect ICT-Based Education Reform to Economic and Social Development - Kozma, Robert B. (Human Technology: An Interdisciplinary Journal on Humans in ICT Environments, 2005)
Information and communication technology (ICT) is a principal driver of economic development and social change, worldwide. In many countries, the need for economic and social development is used to justify investments in educational reform and in educational ICT. Yet the connections between national development goals and ICT-based education reform are often more rhetorical than programmatic. This paper identifies the factors that influence economic growth and shows how they supported economic and social development in three national case studies: Singapore, Finland, and Egypt. It describes a systemic framework of growth factors and types of development that can be used to analyze national policies and connect ICT-based education reform to national economic and social development goals. And it discusses how the coordination of policies within and across ministries can support a nation’s efforts to improve economic and social conditions. The paper highlights special concerns and challenges of developing countries.
shortDOI: 10/gf54xx KerkoCite.ItemAlsoKnownAs: 10.17011/ht/urn.2005355 10/gf54xx 2339240:U6EMQ8ZJ 2339240:XP4CBBBW 2405685:4IF64UER 2405685:MUCISL2Q

Computer-Adaptive Testing for Students with Disabilities: A Review of the Literature - Stone, Elizabeth; Davey, Tim (ETS Research Report Series, 2011)
There has been an increased interest in developing computer-adaptive testing (CAT) and multistage assessments for K-12 accountability assessments. The move to adaptive testing has been met with some resistance by those in the field of special education who express concern about routing of students with divergent profiles (e.g., some students with math-based learning disabilities may have difficulty with basic computation but not high level problem solving) and poor performance on early test questions. This paper consists of a literature review focusing on adaptive testing issues for students with disabilities in the K-12 sector. While it is clear that there are issues that will present obstacles to administering accountability tests adaptively to students with disabilities, this synthesis of research and policy developments with respect to this topic will be useful both for development of research agendas and to inform states that are currently using or are considering moving to CAT.
KerkoCite.ItemAlsoKnownAs: 10.1002/j.2333-8504.2011.tb02268.x 2339240:A69MIC83 2405685:UQW6AGZS

Distance learning in the context of COVID-19: the case of Rwanda - Ngabonzima, Ernest; Isimbi, Roberte; Mwali, Marie Merci; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4706016 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706016 2339240:F62THLX3 2339240:V5PQVKX2 2405685:ADNJFTFA 2405685:CMDUS73G 2405685:T2JBHFBC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Using Educational Games for Sign Language Learning - A SignWriting Learning Game: Case Study - Bouzid, Yosra; Khenissi, Mohamed Ali; Essalmi, Fathi; Jemni, Mohamed (Journal of Educational Technology & Society, 2016)
ABSTRACT Apart from being used as a means of entertainment, computer games have been adopted for a long time as a valuable tool for learning. Computer games can offer many learning benefits to students since they can consume their attention and increase their motivation and engagement which can then lead to stimulate learning. However, most of the research to date on educational computer games, in particular learning versions of existing computer games, focused only on learner with typical development. Rather less is known about designing educational games for learners with special needs. The current research presents the results of a pilot study. The principal aim of this pilot study is to examine the interest of learners with hearing impairments in using an educational game for learning the sign language notation system SignWriting. The results found indicated that, overall, the application is useful, enjoyable and easy to use: the game can stimulate the students' interest in learning such notations.
KerkoCite.ItemAlsoKnownAs: 2339240:DXXIUF8I 2405685:L83ZWRA2
Keywords: ⛔ No DOI found

An interactive system for finding complementary literatures: a stimulus to scientific discovery - Swanson, DR; Smalheiser, NR (Artificial Intelligence, 1997)
An unintended consequence of specialization in science is poor communication across specialties. Information developed in one area of research may be of value in another without anyone becoming aware of the fact. We describe and evaluate interactive software and database search strategies that facilitate the discovery of previously unknown cross specialty information of scientific interest. The user begins by searching MEDLINE for article titles that identify a problem or topic of interest. From downloaded titles the software constructs input for additional database searches and produces a series of heuristic aids that help the user select a second set of articles complementary to the first set and from a different area of research. The two sets are complementary if together they can reveal new useful information that cannot be inferred from either set alone. The software output further helps the user identify the new information and derive from it a novel testable hypothesis. We report several successful tests and applications of the system.
KerkoCite.ItemAlsoKnownAs: 10.1016/S0004-3702(97)00008-8 2405685:LL56VJY4 2486141:DI9NQLCF 2486141:Q4YETKAP
Keywords: _Added-ailr-2024

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
previousshortDOI: 10/ghgk6r previousDOI: 10.5281/zenodo.3884302 EdTechHub.Source: 2405685:6W2UWE89 EdTechHub.Source: <this> shortDOI: 10/ghgk6r KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 10.53832/edtechhub.0041 10/ghgk6r 2129771:2MD2QL8K 2339240:7QEJ68RG 2405685:6W2UWE89 2405685:7HQN2HAD
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Teachers with disabilities: A literature review - Neca, Patrícia; Borges, Maria Leonor; Pinto, Paula Campos (International Journal of Inclusive Education, 2022)
The development of an inclusive education system is regarded as a fundamental pillar for the full participation of persons with disabilities in society. To date, research on inclusive education has been mainly focused on students with disabilities, special education teachers and the role of legislation with less attention being paid to another important player in the implementation of a truly inclusive education system: teachers with disabilities. To address this knowledge gap, in this article we present a literature review, analysing the main ﬁndings and contributions from research that examines issues pertaining to teachers with disabilities. Drawing from 53 articles published in English in peerreview journals, the paper identiﬁes four main research topics: (1) Teachers’ life trajectories, educational practices, and challenges; (2) Teacher’s training; (3) Perspectives about teachers with disabilities (among students and school principals), and (4) the underrepresentation of teachers with disabilities in the literature. We conclude arguing that the research agenda on inclusive education would beneﬁt from including the perspective of teachers with disabilities.
KerkoCite.ItemAlsoKnownAs: 10.1080/13603116.2020.1776779 2339240:67VHG9BE 2405685:75WF9D4K

The Effectiveness and Usability of the Educational Software on Concept Education for Young Children with Impaired Hearing - Goker, Hanife; Ozaydin, Latife; Tekedere, Hakan (EURASIA Journal of Mathematics, Science & Technology Education, 2016)
Early intervention and early education have a special place in educating the children with Impaired Hearing (IH). The advancements in information and communication technologies have led to adopting the view that such technologies could be applied in the educational process of the children with IH. Besides, the positive results acquired in the studies conducted in the light of this review have brought up the fact that proper technology-based educational environments should be provided and popularized for the young children with IH. In this study, educational software has been developed for the purpose of teaching emotions and opposite concepts to young children with IH. With this software, videos with topic descriptions, games reinforcing funny and topic-based learning, questions and audio-visual feedbacks have been used. The effectiveness of this software in concept education along with its usability by children has been examined; and in addition, the subjective viewpoints of the teachers of students with IH on this software have been consulted as well.
KerkoCite.ItemAlsoKnownAs: 10.12973/eurasia.2016.1207a 2339240:LS7NEM49 2405685:CW2LUTWC

School workforce in England, Reporting Year 2020 - UK Government (2021)
This release is largely based on the School Workforce Census. The census collects information from schools and local authorities on the school workforce in state-funded schools in England. Independent schools, non-maintained special schools, sixth-form colleges and further education establishments are not included. The latest data relates to November 2020 and so this is the first data in the series to relate to the coronavirus (COVID-19) pandemic. Coronavirus (COVID-19): Change to statistics To reduce burden on schools and local authorities during the pandemic, data on qualifications and staff absences were not collected in 2020. They will be collected again in 2021. Data on school workforce absence during the pandemic has been collected via the Department's education settings survey. Specific guidance can be found within affected sections of this statistic.
KerkoCite.ItemAlsoKnownAs: 2339240:V4JNURZK 2405685:AARN4AJQ 4656463:2DTJRBXV

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RPKBXC8H 2405685:XNWLCKWJ

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR10.100 2339240:B8RGF7UM 2405685:ZSVGWH7J

The Simple, the Complicated, and the Complex: Educational Reform Through the Lens of Complexity Theory - Snyder, Sean (2013)
This paper explores the nature of complexity theory and its applications for educational reform. It briefly explains the history of complexity theory and identifies the key concepts of complex adaptive systems, and then moves on to define the differences between simple, complicated, and complex approaches to educational reform. Special attention is given to work currently underway in the fields of healthcare, emergency management and ecology that draws on complexity theory to build more resilient and robust response systems capable of adapting to changing needs and of identifying key pressure points in the system. Finally, this paper presents several examples of educational reform programmes undertaken worldwide that have implemented complexity theory principles to achieve positive results. It also recommends involving multiple stakeholders across the different levels of governance structure, increasing lateral knowledge-sharing between schools and districts, and transforming policy interventions to bring greater flexibility to the reform process. This move toward feedback-driven adaptive reform allows for better targeting of programmes to specific contexts and may prove a key way forward for educational policymakers.
Series: OECD Education Working Papers Volume: 96 zotzenLib.CopiedFrom: 2339240:4NV7VJ5R KerkoCite.ItemAlsoKnownAs: 10.1787/5k3txnpt1lnr-en 2339240:4NV7VJ5R 2405685:86KPU7TF

Training with ICT for ICT from the trainee’s perspective. a local ICT teacher training experience - Kalogiannakis, Michail (Education and Information Technologies, 2010)
The introduction of ICT (Information and Communication Technologies) presents new challenges for teachers and often meets with their belief that ICT, as well as other changes present a factor, which can cause several changes in school. Although there have been many education reforms regarding teachers’ training policy in recent years and the number of training programs has been increased, they have not been able to satisfy teachers’ needs to a substantial degree. In this research the results from an exploratory study conducted within the framework of a national training programme in Greece on ICT known as "In-service teacher training in the use of ICT in Education" are presented. Based on a specially constructed questionnaire intended for the educators, this research elicits teachers’ attitudes towards this programme. Some of the main results point out the preparedness of these teachers to use ICT in the daily school practice. Furthermore, they expressed their wish for further in-training programmes concerning the pedagogical development of the ICT use in class practice. KeywordsIn-service training-Teachers-ICT-Greece
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-008-9079-3 2339240:T9FFA6HC 2405685:DXHT4AIY

Teaching linear algebra supported by GeoGebra visualization environment - Aytekin, Cahit; Kiymaz, Yasemin (Acta Didactica Napocensia, 2019)
Linear algebra differs from other mathematics courses because of the special difficulties that students have in understanding the concepts. Teaching without concretizing the concepts of Linear Algebra encouraged students to memorize definitions of concepts and rules has been articulated. Many researches show that technology-supported teaching is effective in concretizing abstract concepts. In this study, it was examined how pre-service mathematics teachers relate the definitions of concepts (linear combination, linear dependency/independency and spanning) and their visual equivalents in R[superscript 2] and R[superscript 3]. The study was conducted with four students who attended the Linear Algebra-2 course in the Elementary Mathematics Teaching, Faculty of Education of a state university in Turkey. The study was conducted by the teaching experiment method. Interviews were conducted using activities prepared in the GeoGebra program. It was observed that the participants used these concepts in very flexible way and they established a relationship between visualization and definitions in a very short time compared to the time spent during an educational period.
Publisher: Babes-Bolyai University, Kogainiceanu 1, Cluj-Napoca, 400084 Romania Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2396823562?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.24193/adn.12.2.7 2339240:BJHHRSRN 2405685:SNEABJDN 2534378:G2ILAXW6 2534378:J8FUJBYM
Keywords: Algebra; Computer Software; Definitions; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Foreign Countries; Higher Education; Mathematics Instruction; Mathematics Teachers; Postsecondary Education; Preservice Teachers; Teaching Methods; Technology Uses in Education; Turkey; Visualization; __:import:01; __:match:final; __:matched; __:study_id:2099267; __finaldtb

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

Floods in Pakistan: Human Development at Risk - Barón, Juan D.; Bend, Mary; Roseo, Elena; Farrakh, Izza (World Bank, 2022)
This note assesses the effects of the 2022 floods on human capital in Pakistan. It focuses on the results of a Pakistan-wide phone survey that gathered information on the experiences of approximately 4,000 families with children ages 3 to 17.
KerkoCite.ItemAlsoKnownAs: 2339240:LLDG8ERK 2339240:RY7788BK 2405685:RJB9PQXN 2405685:W7C2N58F
Keywords: ⛔ No DOI found

Public vs Private Quality Education at Primary Level in Pakistan - Farooq, Muhammad Sabil; Feroze, Nazia; Kai, Yuan Tong (International Online Journal of Primary Education, 2017)
Pakistan is an ethnically and religiously diverse country of over 190 million people. There are 22.6 million boys and girls out of school that's nearly half (44%) of all children in the country. This study was designed to assess comparative quality measures of primary level education at both public and private institutions of Pakistan. This study based on secondary data specially focused on ASER Pakistan Survey Report 2015 that was conducted in 146 rural districts of Pakistan, covering 83,755 households in 4,217 villages throughout the country. Detailed information was collected on 258,021 children (59% males, 41% females) aged 3-16 years. Out of these 219,609 children aged 5-16 years were tested for language and arithmetic competencies. It was found that Public schools lacking with trained teaching staff, well equipped classrooms and good policy and administration. While the other hand private schools deficient of well-educated staff, good infrastructure and self-motivation. It was recommended that the Government needs to realize this situation and to equalize the standards of public and private sector to achieve vigorous quality education at this level.
Publisher: International Online Journal of Primary Education KerkoCite.ItemAlsoKnownAs: 2339240:JRSDGKRM 2405685:BSNTWHMM
Keywords: Academic Achievement; Arithmetic; Educational Administration; Educational Policy; Educational Quality; Educational Resources; Elementary Education; Elementary School Students; Foreign Countries; Literacy; Mathematics Skills; Private Education; Public Education; Secondary School Students; Socioeconomic Influences; Teacher Competencies; ⛔ No DOI found

A computational literature review of the field of System Dynamics from 1974 to 2017 - Kunc, Martin; Mortenson, Michael J.; Vidgen, Richard (Journal of Simulation, 2018)
System Dynamics celebrated its 60th anniversary in 2017. While there have been numerous special issues in diverse journals that bring together work by System Dynamics scholars who share similar research interests, there have been no systematic reviews of scholarly activity across the broad field. This paper presents a computational literature review of the field from 1974 to 2017. A CLR automates the analysis of research articles with analysis of content (topic modelling of abstracts) to identify emergent themes in the literature. We performed a broad review of the field by initially searching using the term “System Dynamics” with more than 8000 articles. However, the results obtained were not satisfactory so we decided to restrict our sample to less than 800 articles from recognised journals and proceedings. After evaluation of the results obtained from topic modelling, we decided to use 51 topics covering most of the articles in our sample. A list of 51 topics provides enough granularity to identify relevant patterns of activity within the community of System Dynamics scholars. For each of these 51 topics, we present a commentary on the key insights obtained.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17477778.2018.1468950 KerkoCite.ItemAlsoKnownAs: 10.1080/17477778.2018.1468950 2405685:KNZA7VQE 2486141:2X7SQ6MJ 2486141:Y3KUR5CN
Keywords: System Dynamics; computational literature review; healthcare; methodology; supply chain

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M7XYZTWF 2405685:C7C3BM9Z

Tailoring education with GenAI: A new horizon in lesson planning - Karpouzis, Kostas; Pantazatos, Dimitris; Taouki, Joanna; Meli, Kalliopi (arXiv, 2024)
The advent of Generative AI (GenAI) in education presents a transformative approach to traditional teaching methodologies, which often overlook the diverse needs of individual students. This study introduces a GenAI tool, based on advanced natural language processing, designed as a digital assistant for educators, enabling the creation of customized lesson plans. The tool utilizes an innovative feature termed 'interactive mega-prompt,' a comprehensive query system that allows educators to input detailed classroom specifics such as student demographics, learning objectives, and preferred teaching styles. This input is then processed by the GenAI to generate tailored lesson plans. To evaluate the tool's effectiveness, a comprehensive methodology incorporating both quantitative (i.e., % of time savings) and qualitative (i.e., user satisfaction) criteria was implemented, spanning various subjects and educational levels, with continuous feedback collected from educators through a structured evaluation form. Preliminary results show that educators find the GenAI-generated lesson plans effective, significantly reducing lesson planning time and enhancing the learning experience by accommodating diverse student needs. This AI-driven approach signifies a paradigm shift in education, suggesting its potential applicability in broader educational contexts, including special education needs (SEN), where individualized attention and specific learning aids are paramount
arXiv:2403.12071 [cs] KerkoCite.ItemAlsoKnownAs: 10.48550/arXiv.2403.12071 2339240:HPBKA7JW 2405685:6A5CLBVW
Keywords: Computer Science - Artificial Intelligence; Computer Science - Computers and Society

Bangladesh GNI per capita 1973-2021 - Macrotrends
GNI per capita (formerly GNP per capita) is the gross national income, converted to U.S. dollars using the World Bank Atlas method, divided by the midyear population. GNI is the sum of value added by all resident producers plus any product taxes (less subsidies) not included in the valuation of output plus net receipts of primary income (compensation of employees and property income) from abroad. GNI, calculated in national currency, is usually converted to U.S. dollars at official exchange rates for comparisons across economies, although an alternative rate is used when the official exchange rate is judged to diverge by an exceptionally large margin from the rate actually applied in international transactions. To smooth fluctuations in prices and exchange rates, a special Atlas method of conversion is used by the World Bank. This applies a conversion factor that averages the exchange rate for a given year and the two preceding years, adjusted for differences in rates of inflation between the country, and through 2000, the G-5 countries (France, Germany, Japan, the United Kingdom, and the United States). From 2001, these countries include the Euro area, Japan, the United Kingdom, and the United States.
KerkoCite.ItemAlsoKnownAs: 2339240:ACPLQN5F 2405685:SDGDR87J

When does ICT support education in South Africa? The importance of teachers' capabilities and the relevance of language - Gudmundsdottir, G. B. (Information Technology for Development, 2010)
The aim of this paper is to highlight some of the challenges of information and communication technology (ICT) integration in a South African classroom setting. The main focus is on the concept of a digital divide, and how cultural complexity with special emphasis on language can affect the divide in schools that already have material access to ICT. The study is based on fieldwork in seventh-grade classes in four primary schools in Cape Town, South Africa. The learners answered a questionnaire regarding their ICT use and skills, and interviews were conducted with learners, teachers, and principals. In conclusion, it is argued that the challenges of language in South African schools can exacerbate or maintain the digital divide among learners who are already disadvantaged due to a range of social inequalities. For learners to fully master the use of ICT in today's global knowledge society, it needs to be put in a local context, which includes use in a familiar language. Moreover, it is suggested that greater opportunities for teacher training are needed in order to enhance culturally sensitive and appropriate ICT integration based on local needs and capacity.
Publisher: Routledge _eprint: https://doi.org/10.1080/02681102.2010.498409 KerkoCite.ItemAlsoKnownAs: 10.1080/02681102.2010.498409 2405685:U9M2N3BV 4042040:YQYVKVPN
Keywords: ICT integration; digital divide; disadvantaged learners; language of teaching and learning; teacher training

The Impact of ICT as Another Route to Overcome Learning Barriers for Students with SEN: A Case Study in an Egyptian Context - Al-Gawhary, Wedad; Kambouri, Maria (International Association for the Development of the Information Society, 2012)
The purpose of this case study was to measure the impact of using ICT in Individual Learning Programmes of students with learning disabilities. Twenty five students and thirteen teachers took part in the research which was based on classroom observations. The Kappa coefficient was employed as a measure to statistically quantify the students' acquisition and progress in learning computer and literacy skills through raters' observations. A high correlation between Keyboard, PowerPoint, and literacy skills (writing, reading, and maths) was revealed suggesting the significance and impact of keyboard training as an essential component towards achieving educational objectives. Moreover, thematic analysis of the teachers' interviews provided a further dimension for understanding factors influencing the ICT integration process. These results further confirmed the positive impact of computer skills training on the students' learning experience which also revealed a strong belief in the right of every child to all learning opportunities, particularly ICT regardless of his/her abilities.(Contains 2 tables.) [For the complete proceedings, "Proceedings of the International Association for Development of the Information Society (IADIS) International Conference on Cognition and Exploratory Learning in Digital Age (CELDA) (Madrid, Spain, October 19-21, 2012)," see ED542606.]
Publication Title: International Association for Development of the Information Society KerkoCite.ItemAlsoKnownAs: 2339240:95DQ5J33 2405685:M5TD7M7N
Keywords: Autism; Barriers; Case Studies; Cerebral Palsy; Communications; Computer Literacy; Computer Mediated Communication; Computer Software; Down Syndrome; Foreign Countries; Heterogeneous Grouping; Information Technology; Interrater Reliability; Mixed Methods Research; Semi Structured Interviews; Semitic Languages; Special Needs Students

Mobile learning and student cognition: A systematic review of PK-12 research using Bloom’s Taxonomy - Crompton, Helen; Burke, Diane; Lin, Yi-Ching (British Journal of Educational Technology, 2019)
The rise of mobile learning in schools during the past decade has led to promises about the power of mobile learning to extend and enhance student cognitive engagement. The purpose of this study was to examine trends to determine the cognitive level students are involved in within mobile learning activities. This systematic review involved an aggregated and configurative synthesis of PK-12 mobile learning studies from 2010 to 16 and used Bloom’s Taxonomy as a theoretical framework for categorizing the cognitive level of student activities. Major new findings include that students are involved in activities at all six levels of Bloom’s Taxonomy. This study shows that over 60% of researchers are developing activities that require high levels of cognitive processing, a large increase from past studies. Nonetheless, 40% are integrating mobile devices in ways that keep students working with minimal cognitive processing. In both elementary and secondary studies, there was a 40/60% split in the use of lower versus high level thinking opportunities. New findings show that mobile devices were integrated into science, mathematics, social studies, literacy, art and special education. Studies in science settings were the majority of the studies (40%), followed by literacy (24%).
shortDOI: 10/gf5f7g KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12674 10/gf5f7g 2339240:ITSJB3B5 2339240:KIEJIK2D 2405685:J23Q8BH4
Keywords: Reviewed

Teachers' and Pupils' Experiences of Integrated Education in Uganda - Arbeiter, Susanne; Hartley, Sally (International Journal of Disability, Development and Education, 2002)
Under the Universal Primary Education (UPE) programme in Uganda, which was implemented in 1997, the idea of integrated education was put into practice. Today children with disabilities are enrolled in regular primary schools in the whole country. After three years of experience with UPE, the aim of this study was to examine the views of teachers about their needs for training and support regarding the task of teaching children with disabilities in ordinary classrooms. A qualitative approach was chosen using individual interviews, focus group discussions with teachers, pupils and head teachers, and observations in classrooms. Three primary schools in different districts of Uganda were selected as research sites. For a number of reasons data collection from the pupils proved problematic but generally the ndings con rmed the information drawn from the review of literature. In addition to the high teacher–pupil ratio, there is an alarming lack of resources in the schools and an urgent need for teacher training to meet special needs in the classroom. Despite these dif cult conditions found in schools, many teachers had positive attitudes towards integrating children with disabilities, but only a few examples from the classroom observations showed good practice for meeting a diversity of needs.
shortDOI: 10/frj9zc KerkoCite.ItemAlsoKnownAs: 10.1080/10349120120115334 10/frj9zc 2405685:QR783YSK

Accessibility - Wikipedia (Wikipedia, 2020)
Accessibility in the sense considered here refers to the design of products, devices, services, or environments so as to be usable by people with disabilities. The concept of accessible design and practice of accessible development ensures both "direct access" (i.e. unassisted) and "indirect access" meaning compatibility with a person's assistive technology (for example, computer screen readers). Accessibility can be viewed as the "ability to access" and benefit from some system or entity. The concept focuses on enabling access for people with disabilities, or special needs, or enabling access through the use of assistive technology; however, research and development in accessibility brings benefits to everyone.Accessibility is not to be confused with usability, which is the extent to which a product (such as a device, service, or environment) can be used by specified users to achieve specified goals with effectiveness, efficiency, convenience satisfaction in a specified context of use.Accessibility is strongly related to universal design which is the process of creating products that are usable by people with the widest possible range of abilities, operating within the widest possible range of situations. This is about making things accessible to all people (whether they have a disability or not).
Page Version ID: 984895511 KerkoCite.ItemAlsoKnownAs: 2405685:UQE9CKPF

Tiblo: a tangible learning aid for children with dyslexia - Pandey, Sumit; Srivastava, Swati (Procedings of the Second Conference on Creativity and Innovation in Design, 2011)
Dyslexia is a learning disability, which affects the ability to read and spell correctly. Special schools for children with dyslexia focus on individual growth, learning and psychological difficulties faced by the child. In this paper, we describe the design, development and testing of Tiblo (Tangible Interactive BLOcks), a tangible learning aid for children with dyslexia in the age group of 8 to 12 years. Tiblo has been specifically designed keeping in mind the psychological and emotional effects of dyslexia. We explain the process and results of an ethnographic study conducted at a school for children with dyslexia; the resulting concept development and prototyping. Further, we outline the testing process with the students at the school and the results of the same. The results showed that the children have a greater engagement in their classroom activities and there is an improvement in their retention abilities on using Tiblo. Also, they had a very strong sense of attachment and ownership towards the blocks and like to personalize it. This was in sharp contrast with other digital learning aids which offer a symptomatic and subject specific approach to aiding children with dyslexia and hence do not develop a personal one to one relationship with the child.
KerkoCite.ItemAlsoKnownAs: 10.1145/2079216.2079247 2339240:99N4A4R8 2405685:ACZ65MR7
Keywords: collaborative learning; design case study; dyslexia; emotional design; interaction design; learning aids; play and learn; tangible user interfaces

The design and testing of multimedia for teaching arithmetic to deaf learners - Techaraungrong, Piyaporn; Suksakulchai, Surachai; Kaewprapan, Wacheerapan; Murphy, Elizabeth (Education and Information Technologies, 2017)
The purpose of the study reported on in this paper was to design and test multimedia for deaf and hard of hearing (DHH) learners. The study focused on counting, addition and subtraction with grade one (age 7) DHH learners in Thailand. The multimedia created for the study was informed by design considerations for DHH learners of arithmetic and aimed to minimize cognitive load. Testing took place over a period of 16 weeks during which learners alternated between 2 and 3 week sessions of one hour per day with multimedia (numbers 1–10) versus 2–3 week sessions of one hour per day with the teacher (numbers 11–20). Results of the design included features such as non-essential use of text, reliance on non-symbolic objects, user control, and signals to relevant content. Results of testing showed that learning with multimedia resulted in higher scores than learning with the teacher (Z = 4.545, p = 0.000). Post-intervention interviews highlighted the role of motivation, ease of comprehension and independent learner control of the multimedia. The conclusion highlighted the need for multimedia design principles that reflect a more inclusionary focus on children with special needs such as those featured in this study.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9441-1 2339240:CZT5XWYH 2405685:DK3Y33G7

Working for my dreams - a Tanzanian OLPC experience - Duveskog, M.; Sedano, C. I.; Sutinen, E. (2010 IST-Africa, 2010)
Students at Tumaini University in Tanzania won a prestigious OLPC project where Ukombozi primary school in Tanzania was given 100 XO laptops for the children at the school. After teachers and students had undertaken basic training in using the laptops the workshop “Working for my Dreams” was organized at the school. The XO laptop, specially designed for young learners in developing countries showed a number of short comings including the poor functionality of the mouse, difficulties in installing additional applications and the limited storage space, which raised several questions around the technology and its usefulness. Much time was spent on figuring out solutions on how to use the XO laptops for basic things such as showing recorded videos in the browser which would have been minor tasks on any other commercially available platform. The outcome of the workshop was however a success and XO was eventually able to perform according to our needs for the workshop. We will evaluate the XO platform based on the context of Ukombozi primary school and on the tasks required of the XO laptop for the success of the workshop. The technical challenges encountered during the workshop and our solutions in overcoming the challenges will be discussed.
KerkoCite.ItemAlsoKnownAs: 2339240:JL9XPEWL 2405685:PG3IVJWK
Keywords: Conferences; Context; Educational institutions; Human immunodeficiency virus; Materials; OLPC; OLPC project; Portable computers; Tanzania; Tumaini University; Ukombozi primary school; XO; XO laptops; application installation; computer based training; context; developing countries; dreams; educational institutions; laptop computers; mouse; mouse controllers (computers); storage space; training; working for my dreams; workshop; ⛔ No DOI found

The design and testing of multimedia for teaching arithmetic to deaf learners - Techaraungrong, Piyaporn; Suksakulchai, Surachai; Kaewprapan, Wacheerapan; Murphy, Elizabeth (Education and Information Technologies, 2015)
The purpose of the study reported on in this paper was to design and test multimedia for deaf and hard of hearing (DHH) learners. The study focused on counting, addition and subtraction with grade one (age 7) DHH learners in Thailand. The multimedia created for the study was informed by design considerations for DHH learners of arithmetic and aimed to minimize cognitive load. Testing took place over a period of 16 weeks during which learners alternated between 2 and 3 week sessions of one hour per day with multimedia (numbers 1–10) versus 2–3 week sessions of one hour per day with the teacher (numbers 11–20). Results of the design included features such as non-essential use of text, reliance on non-symbolic objects, user control, and signals to relevant content. Results of testing showed that learning with multimedia resulted in higher scores than learning with the teacher (Z = 4.545, p = 0.000). Post-intervention interviews highlighted the role of motivation, ease of comprehension and independent learner control of the multimedia. The conclusion highlighted the need for multimedia design principles that reflect a more inclusionary focus on children with special needs such as those featured in this study.
8 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9441-1 2339240:EEJYTIKF 2405685:DDVUKNXB
Keywords: Arithmetic; Cognitive load; Deaf and hard of hearing; Design; Multimedia; Testing; ⛔ No INSPIRE recid found

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Trends in educational research about e-learning: a systematic literature review (2009–2018) - Valverde-Berrocoso, Jesús; Garrido-Arroyo, María del Carmen; Burgos-Videla, Carmen; Morales-Cevallos, María Belén (Sustainability, 2020)
The concept of e-learning is a technology-mediated learning approach of great potential from the educational perspective and it has been one of the main research lines of Educational Technology in the last decades. The aim of the present systematic literature review (SLR) was to identify (a) the research topics; (b) the most relevant theories; (c) the most researched modalities; and (d) the research methodologies used. To this end, the PRISMA protocol was followed, and diﬀerent tools were used for the bibliographic management and text-mining. The literature selection was carried out in three ﬁrst-quartile journals indexed in JCR-SSCI specialized in Educational Technology. A total of 248 articles composed the ﬁnal sample. The analysis of the texts identiﬁed three main nodes: (a) online students; (b) online teachers; and (c) curriculum-interactive learning environments. It was revealed that MOOC was the most researched e-learning modality. The Community of Inquiry and the Technological Acceptance Model, were the most used theories in the analyzed studies. The most frequent methodology was case study. Finally, the conclusions regarding the objectives of our SRL are presented: Main themes and research sub-themes, most researched e-learning modality, most relevant theoretical frameworks on e-learning, and typologies of research methodologies.
KerkoCite.ItemAlsoKnownAs: 10.3390/su12125153 10/ghvnfd 2339240:CMZ8HVYI 2405685:EWKSK6YI

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
ZenodoArchiveID: 4706036 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706036 2339240:CB8D4LUQ 2339240:METE88UD 2339240:MK55NVDC 2339240:Z3EF9Q75 2405685:3XIBJD8G 2405685:3Y33YNL3 2405685:8JZVGC6W 2405685:HBXKVKMA 2405685:QJ783WH5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Community Development through Open Learning and Distance Education - Mehmood, Tahir; Hussain Ch, Abid; Saeed, Amna (Bulletin of Education and Research, 2016)
The global need for community development is greater now in the early 21st century than ever before. According to UNESCO, half of the world's 195 countries will have to expand their stock of educationist significantly, some by tens of thousands, if the goal development targets are desired to achieve. Socioeconomic inequities, political instability, demographic changes and crises such as the HIV/AIDs epidemic have engendered huge shortfalls in teacher supply and low teacher quality in many developing countries. Education serves as back bone in development process. Open learning and distance education programs are serving as pivotal part of development process. It is now clear that "bricks and mortar" approaches to expanding teacher education may not be adequate if the current and projected shortfalls in teacher supply and low teacher quality are to be properly addressed. The study is designed to measure the perceptions of teaching learning community about community development with special reference to open and distance learning. It was descriptive study which targeted teachers, students, community members and experts. Data analysis was carried out by using statistical techniques served by SPSS. Findings reflected that audience perceives open and distance learning as change agent and as development tool. It is noticed that target audience has driven prominent performance by using facility of open and distance learning.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:VXX3G7KQ 2405685:GTVRNDQ9
Keywords: Access to Education; Change Agents; Community Development; Developing Nations; Distance Education; Economic Development; Educational Change; Educational Quality; Foreign Countries; Gender Differences; Nongovernmental Organizations; Open Educational Resources; Social Differences; Specialists; Student Attitudes; Teacher Attitudes; Teacher Shortage; ⛔ No DOI found

Gender differences in computer and information literacy: An in-depth analysis of data from ICILS - Gebhardt, Eveline; Thomson, Sue; Ainley, John; Hillman, Kylie (Springer Nature, 2019)
This open access book presents a systematic investigation into internationally comparable data gathered in ICILS 2013. It identifies differences in female and male students’ use of, perceptions about, and proficiency in using computer technologies. Teachers’ use of computers, and their perceptions regarding the benefits of computer use in education, are also analyzed by gender. When computer technology was first introduced in schools, there was a prevailing belief that information and communication technologies were ‘boys’ toys’; boys were assumed to have more positive attitudes toward using computer technologies. As computer technologies have become more established throughout societies, gender gaps in students’ computer and information literacy appear to be closing, although studies into gender differences remain sparse. The IEA’s International Computer and Information Literacy Study (ICILS) is designed to discover how well students are prepared for study, work, and life in the digital age. Despite popular beliefs, a critical finding of ICILS 2013 was that internationally girls tended to score more highly than boys, so why are girls still not entering technology-based careers to the same extent as boys? Readers will learn how male and female students differ in their computer literacy (both general and specialized) and use of computer technology, and how the perceptions held about those technologies vary by gender.
Accepted: 2020-03-18 13:36:15 Journal Abbreviation: An In-depth Analysis of Data from ICILS KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-26203-7 2339240:WGHTZ8T5 2405685:7BDLRHWK

The Views of University Students About the Achievements and Motivations of the Distance Education Process During the Pandemic Period - Güldal Kan, Şebnem; Çaltıkuşu, Çilem; Şensoy, Şeniz (Propósitos y Representaciones, 2021)
The aim of this study is to examine the views of students about the achievements and motivations of thedistance education processes in universities during the pandemic period. The working group consists of 68 prospective teachers who continue their undergraduate programs in different departments of a private university in Northern Cyprus in the 2019-2020 spring academic year. All these participantsarestudying at thevariousdepartments of theFaculty of Education as 17 are in Pre-school Education, 28 in PrimaryEducationMathematics, 6 in PrimaryEducation, 1 in HistoryTeaching, 12 in Special Needs Education, 4 of them arestudying in Guidance and Psychological Counseling. The study is a qualitative study and the design of the study is determined as a case study. 42 female and 26 male teacher candidates participated in the study group. The majority of the participants are prospective teachers studying in their final year at university. While choosing the participants, easily accessible case sampling from purposeful sampling type was used. A Semi-structured interview form was used as a toolfordata collection. Later, the opinions of the experts were obtained and the interview questions were re-arranged accordingly and applied to the participants. As a result of the research, it was concluded that the psychological trauma experienced by teacher candidates during distance education at thepandemicperiodaffects both the success and motivation of their lessons.
KerkoCite.ItemAlsoKnownAs: 10.20511/pyr2021.v9nSPE3.1165 2339240:3524XZX7 2405685:AE8RCH6V

Mother Tongue Education: The West African Experience - Bamgbose, Ayo (Hodder and Stoughton Ltd, 1976)
In the rapidly changing political, economic, and social life of West Africa, there is a renewed interest in cultural identity. This book describes the developments and the difficulties experienced by different West African countries in the use of mother tongues in multi-lingual society. The book was commissioned to give scholars, educators, and policy-makers concerned with mother tongue education an account of developments in selected countries. Three broad areas are covered: (1) situations where the mother tongue has not yet been introduced into the formal school system but where preparations are being made; (2) situations where there has been a long tradition of mother tongue education; and (3) special projects. An introduction discusses the role of the mother tongue in education, with particular reference to West Africa. This is followed by a historical sketch of developments in mother tongue education. Contributions from Sierra Leone and Dahomey cover the first of the areas mentioned. Ghana's report covers the second area. The last two reports, from Nigeria, fall into the third category. Finally, two projects are described: the Six-Year Primary Project on the use of a major language as a medium of instruction and the Rivers Readers Project on the introduction of smaller languages into the formal school system. (Author/AM)
KerkoCite.ItemAlsoKnownAs: 2405685:ZZ97PBUU 4042040:G8B7QARM
Keywords: African Culture; African Languages; Bilingual Education; Educational Planning; French; Igbo; Language Planning; Language of Instruction; Mandingo; Mende; Multilingualism; Native Speakers; Portuguese; Regional Dialects; Sociolinguistics; Susu; Uncommonly Taught Languages; Wolof; Yoruba

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: <this> EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:6TX2RFBC 2405685:BGLPB3AG
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoODE

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Teaching children with disabilities: ICTs in Bangkok and Addis Ababa - Schiemer, Margarita; Proyer, Michelle (Multicultural Education & Technology Journal, 2013)
Purpose – This paper intends to explore the levels of availability and restrictions in relation to the use of ICTs (information and communication technologies) for educating children with disabilities in Thailand's and Ethiopia's capitals. Design/methodology/approach – In the course of an international research project, parents and teachers of children with different disabilities, the children themselves and further experts were interviewed about barriers and facilitators in the children's educational environment. For this paper only selected interviews focusing on sensory disabilities were analysed regarding the above mentioned areas of using ICTs. Findings – ICTs are available in the respective cities. The levels of restrictions related to the socio‐economic situation in the two cities vary accordingly but show the same overall limitations. The intensity and kind of use of ICTs is strongly related to resources, the educational actors' awareness and knowledge. Originality/value – Approaching the topic of ICTs in relation to disability might not be new, neither is the contextualisation with the Majority World. However, the combination of the three aspects against the background of current global developments (e.g. the growing gap between the poor and the rich) reveals the importance of taking a closer look at special needs education and ICTs in the Majority World. This opens the floor for discussion on how inclusion of the most marginalised groups in education affects development in general.
3 citations (Crossref) [2024-02-28] Publisher: Emerald Group Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/17504971311328026 2339240:8W9UMMQG 2339240:HT2CTPM2 2405685:5AVSEAD3 2405685:6SYB238I
Keywords: Children; Children with disabilities; Comparative research; Disabilities; Education; Ethiopia; ICTs; Majority World; Thailand; include (age level unclear); ⛔ No INSPIRE recid found

Games for enhancing basic reading and maths skills: A systematic review of educational game design in supporting learning by people with learning disabilities - Lämsä, Joni; Hämäläinen, Raija; Aro, Mikko; Koskimaa, Raine; Äyrämö, Sanna-Mari (British Journal of Educational Technology, 2018)
The development of games for people with learning disabilities is one way to enhance the quality of learning and respond to the need for inclusive special educational support. Recently, game researchers have highlighted the need for paying more attention to identifying the game design choices that can strengthen learning. This paper reviews recent studies in the field of games that aim at supporting people with difficulties in learning, particularly in basic reading and maths skills. We identify the major characteristics and learning outcomes of the reviewed studies, as well as key design principles that have been used in games for enhancing basic reading and maths skills. The results show that people with specific learning difficulties have positive improvements in the quality of learning. We also found specific gamification elements that have been used to promote the learning of basic reading and maths skills. However, we call for research, which would explicitly examine the effects of game design choices on learning. Currently, the studies that address learning disabilities do not specifically define which kind of games and game design the results refer to, while game design studies do not clarify how these games influence learning. Thus, there is a need to rethink previous empirical studies on game settings for people with learning difficulties via advancing the role of game design in empirical intervention studies.
shortDOI: 10/gd2h8p KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12639 10/gd2h8p 2339240:FUFE3LCB 2405685:RTFGP4FK
Keywords: Reviewed

Teaching children with disabilities: ICTs in Bangkok and Addis Ababa - Schiemer, Margarita; Proyer, Michelle; Ahamer, Gilbert (Multicultural Education & Technology Journal, 2013)
Purpose – This paper intends to explore the levels of availability and restrictions in relation to the use of ICTs (information and communication technologies) for educating children with disabilities in Thailand's and Ethiopia's capitals. Design/methodology/approach – In the course of an international research project, parents and teachers of children with different disabilities, the children themselves and further experts were interviewed about barriers and facilitators in the children's educational environment. For this paper only selected interviews focusing on sensory disabilities were analysed regarding the above mentioned areas of using ICTs. Findings – ICTs are available in the respective cities. The levels of restrictions related to the socio‐economic situation in the two cities vary accordingly but show the same overall limitations. The intensity and kind of use of ICTs is strongly related to resources, the educational actors' awareness and knowledge. Originality/value – Approaching the topic of ICTs in relation to disability might not be new, neither is the contextualisation with the Majority World. However, the combination of the three aspects against the background of current global developments (e.g. the growing gap between the poor and the rich) reveals the importance of taking a closer look at special needs education and ICTs in the Majority World. This opens the floor for discussion on how inclusion of the most marginalised groups in education affects development in general.
KerkoCite.ItemAlsoKnownAs: 10.1108/17504971311328026 2339240:V5YTXAA5 2405685:2KZYYG9Y
Keywords: Children; Children with disabilities; Comparative research; Disabilities; Education; Ethiopia; ICTs; Majority World; Thailand

Academic and social effects of inclusion on students without disabilities: A review of the literature - Kart, Ayse; Kart, Mehmet (Education Sciences, 2021)
In many countries, educational practices are changing to inclusive education. Inclusive education is educating students with disabilities in general education classrooms with their peers without disabilities. If inclusive education is spreading, research needs to investigate the effects of inclusion not only for students with special needs but also for typically developing students. However, there is more research on the outcomes of inclusion for students with disabilities and less for students without disabilities in inclusive settings. Research shows academic and social gains for students with disabilities, but there is less clarity regarding the influence of inclusion on general education students. Therefore, the purpose of this review is to summarize and organize the literature on the academic and social outcomes of inclusion on students without disabilities. Academic effects of inclusion on students without disabilities are mixed, and the levels of schooling may have a differential impact on the achievement of students without disabilities. The literature indicates mostly positive or neutral effects of inclusion on the academic achievement of typically developing students in the lower grades, whereas neutral or negative influence is indicated for later grades. Additionally, students without disabilities have socially benefited from being in inclusive classrooms with students with disabilities. Mainly, the social effects of inclusion are reduction of fear, hostility, prejudice, and discrimination as well as increase of tolerance, acceptance, and understanding.
32 citations (Crossref) [2024-04-17] Number: 1 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci11010016 2339240:IUXFBDKW 2405685:F5W6PCVI
Keywords: academic achievement; inclusion; social effects; students without disabilities; ⛔ No INSPIRE recid found

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Publisher: Routledge _eprint: https://doi.org/10.1080/03050068.2017.1338641 KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2405685:9FVX5LB3
Keywords: Education; Liberia; Sierra Leone; teachers; teaching about conflict; transitional justice

A Study of the Application of Information Technology in Distance Education in Pakistan - Gujjar, Aijaz Ahmed; Ahmed, Saira Ijaz; Ramzan, Muhammad (Journal of Educational Technology, 2011)
Education plays a vital role to develop the nation culturally, economically and socially. That is why every nation focuses on this sector. For its improvement all endeavors are being made through formal education, Non-formal education and Distance Education. The trend of distance education has developed considerably in developed countries and developing countries. Information technology plays a pivotal role for the development of Distance Education. Keeping in view the importance of I.T. in education, this study was developed. The main aim of this study was to investigate the use of information technology in distance education in Pakistan. Population comprised of the I.T. users, person helping, operating or supervising the I.T. tools as planners, academicians, designers, programmers, producers, operators, regional directors and Deans of AIOU. Questionnaire on five point Likert scale was prepared. Collected data was tabulated and analyzed. The main conclusions of the study are: The use of information technology is still limited. Computer net work was not used for distance learners, Radio, T.V. programs and relevant audio material, videocassettes were prepared and CDs, software still not in use. University library was not computerized. Staff got training from time to time in I.T. Education in their specialization. But there is need to make I.T. system more sophisticated according to new trends and students' needs. There is also need to develop regional centers, which should serve as resource centers to the facilitation of distance learners.
Publisher: i-manager Publications KerkoCite.ItemAlsoKnownAs: 10.26634/jet.7.4.1389 2339240:GMBSS6P7 2405685:F2XC3TFE
Keywords: Access to Information; Data Analysis; Data Collection; Distance Education; Electronic Libraries; Foreign Countries; Information Technology; Likert Scales; Nonformal Education; Open Universities; Questionnaires; Radio; Scores; Statistical Analysis; Student Needs; Technology Uses in Education; Television; Trend Analysis; Use Studies

Remote eye-tracking for cognitive telerehabilitation and interactive school tasks in times of COVID-19 - Iannizzotto, Giancarlo; Nucita, Andrea; Fabio, Rosa Angela; Caprì, Tindara; Bello, Lucia Lo (Information (Switzerland), 2020)
In the attempt to mitigate the effects of COVID-19 lockdown, most countries have recently authorized and promoted the adoption of e-learning and remote teaching technologies, often with the support of teleconferencing platforms. Unfortunately, not all students can benefit from the adoption of such a surrogate of their usual school. We were asked to devise a way to allow a community of children affected by the Rett genetic syndrome, and thus unable to communicate verbally, in writing or by gestures, to actively participate in remote rehabilitation and special education sessions by exploiting eye-gaze tracking. As not all subjects can access commercial eye-tracking devices, we investigated new ways to facilitate the access to eye gaze-based interaction for this specific case. The adopted communication platform is a videoconferencing software, so all we had at our disposal was a live video stream of the child. As a solution to the problem, we developed a software (named SWYG) that only runs at the "operator" side of the communication, at the side of the videoconferencing software, and does not require to install other software in the child's computer. The preliminary results obtained are very promising and the software is ready to be deployed on a larger base. While this paper is being written, several children are finally able to communicate with their caregivers from home, without relying on expensive and cumbersome devices.
KerkoCite.ItemAlsoKnownAs: 10.3390/info11060296 2405685:8EIPHM8H
Keywords: COVID-19; Remote interactive education; Telerehabilitation; Video conferencing; Video-based eye-gaze tracking

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

International review of the literature of evidence of best practice models and outcomes in the education of blind and visually impaired children - Douglas, Graeme; McLinden, Mike; Steve, McCall; Pavey, Susan; Ware, J; Farrell, A (National Council for Special Education (NCSE), 2010)
KerkoCite.ItemAlsoKnownAs: 2339240:45QZZCB8 2405685:MZA7MRZ8

Indian educators' awareness and attitude towards assistive technology - Kundu; Bej, Tripti (Journal of Enabling Technologies, 2020)
Objective: This study investigated the awareness and attitude of Indian mainstream secondary school teachers on assistive technologies (AT) and its implementation level in inclusive setting. Methodology: The study followed descriptive survey method within ex-post-facto research design taking 150 teachers including 15 headmasters from 15 secondary schools as samples following stratified random sampling technique. Questionnaires and interviews (according to set interview protocol) were the main research tools used during survey. Collected data were analyzed descriptively and inferentially to reach a conclusion. Findings: Findings revealed that Indian mainstream secondary school teachers’ awareness of AT was very poor yet their attitude towards it was highly positive. Except having a good attitude, everywhere- the teachers’ knowledge, professional support, or infrastructural support- the inadequacy was obvious. Indian schools were running with a poor resource pool of assistive products along with poor implementation. Hence special need students of these schools were not getting the necessary supports from schools as they deserve which has been hampering the overall inclusive atmosphere of the country. Statistical analysis revealed that male teachers showed slightly higher awareness level regarding AT than their female counterparts but in respect of attitude they were found overpowered by the females. Teachers of urban schools also exhibited slightly better awareness and attitude towards AT than the teachers of rural schools. Lack of suitable policies, adequate awareness and financial limitations were evolved as major barriers in the implementation of AT in these schools.
KerkoCite.ItemAlsoKnownAs: 10.1108/JET-04-2020-0015 2339240:4L9AFNDX 2405685:3SG4D2ZC

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Why the World Needs a Curriculum Alignment Hub - Chandra, Shivi (Learning Equality, 2020)
ZenodoArchiveID: 5534235 previousDOI: 10.5281/zenodo.4314923 previousDOI: 10.5281/zenodo.4768580 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4314923 10.5281/zenodo.4768580 10.53832/edtechhub.0046 2339240:XFMP94YR 2405685:2RMKAHXF 2405685:TLNPJ4IA 2405685:ZNQYTUVV
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgk65 previousDOI: 10.5281/zenodo.3830951 shortDOI: 10/ghgk65 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3830951 10.5281/zenodo.3830951 10.53832/edtechhub.0030 10/ghgk65 2339240:2AU72ZG2 2339240:3DWURGVT 2339240:KMTF4A22 2339240:L86PMYJ2 2339240:PRSHWWK5 2405685:4TKSDH2I 2405685:97JHVZU9 2405685:GUJ3TBS3 2405685:NA8X7J9C 2405685:S3EKNHHG 2405685:XGAFJNAD 4656463:PU6FSTAF
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Place: Limerick Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1430572667?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-10-2012-0052 2339240:C7CEXRWM 2339240:XN53EQR3 2405685:AFTT7Q76 2405685:UYED6EDY 2405685:ZZ7VUU4G 2534378:32ICX4DB 2534378:UTXP2X7Q
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics–Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

A Comparative Study of Online and Directly Selected Secondary School Teachers Regarding Teaching Proficiency and Classroom Management in Kohat Division, Pakistan - Suleman, Qaiser; Hussain, Ishtiaq (International Journal of Learning and Development, 2013)
Secondary school teachers occupy the most critical and crucial position in the entire education system (Suleman, et al, 2011a). The purpose of the study was to compare the performance of online and directly selected secondary school teachers regarding teaching proficiency and classroom Management. All the students at secondary school level in Kohat Division, Khyber Pakhtunkhwa (Pakistan) constituted the population of the study. Only 600 students studying at secondary school level in Kohat Division were selected as sample randomly. The study was delimited to only male students at secondary school level. The study was descriptive type and questionnaire was used as research instrument. Data was collected through personal visits. After the collection of data, it was organized, tabulated, analyzed and interpreted. The statistical tools i.e. means, standard deviation and differences of means were computed for each variable. Significance of difference between the mean values of the responses of students about online and directlly selected secondary school teachers were tested at 0.05 levels by applying t-test. After statisitcal analysis of the data, the researchers conclduded that the overall performance of the directly selected secondary school teachers was better and satisfactory. They were found to have the knowledge of teaching methods and the ability to control classroom disruptive behaviour. Conversely, the overall performance of the online selected secondary school teachers was poor and unsatisfactory. They have no knowledge of teaching methodologies and subject mastery. They were found unable to manage classroom disruptive behaviour and other related activities. Based on findings, it was strongly recommended that a special professional training programme should be arranged to the existing online selected SSTs in teaching methodologies and classroom management to equip them with the modern teaching methods and techniques of managing classroom behaviour so that they become able to perform their duties effectively.
Number: 3 KerkoCite.ItemAlsoKnownAs: 10.5296/ijld.v3i3.4130 2339240:MKBAFBWM 2405685:856AQDD2

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652042 2339240:TJNJX997 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Investigating the mediating role of online learning motivation in the COVID-19 pandemic situation in Bangladesh - Rahman, Md. H Asibur; Uddin, Mohammad Shahab; Dey, Anamika (Journal of Computer Assisted Learning, 2021)
The purpose of this paper is to investigate the mediating role of online learning motivation (OLM) in the COVID-19 pandemic situation in Bangladesh by observing and comparing direct lectures (DL), instructor–learner interaction (ILI), learner–learner interaction (LLI), and internet self-efficacy (ISE) as predictors of OLM and online learning satisfaction (OLS). Data were collected from 442 undergraduate and graduate students from more than 35 universities in Bangladesh. To test the hypotheses, the PLS-SEM approach was applied using SmartPLS 3.0. The study shows a significant mediating role of OLM between the independent variables and learning satisfaction. In addition, DL, ILI, and ISE are shown to be significant predictors of student satisfaction. The findings have a number of valuable implications for education policy makers, universities, instructors, and students. Moreover, the study suggests some new research perspectives to overcome the limitations of this research and to gain precise knowledge on students' learning motivation and satisfaction regarding other online classes for different categories of students (e.g., high school and college, professional, and PhD).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12535 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12535 2339240:D2LCXIHU 2405685:DUEDNPFM
Keywords: Bangladesh; COVID-19; interactions; learning motivation; learning satisfaction; online education

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
ZenodoArchiveID: 7421516 ZenodoArchiveConcept: 7421515 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7421516 10.53832/edtechhub.0143 2405685:DE7XUSMJ 2405685:IWFRG7US 2486141:MQHWRFUH
Keywords: _r:AddedByZotZen

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Examination of Teacher Candidates' Views on Peer Learning Performed with Interactive Videos in the Blended Learning Process - Ipek, Jale; Kalay, Abdullah; Ertas, Sercan (Education Quarterly Reviews, 2021)
Today, the speed of the development of technology has various effects in many areas. In the field of education, some concepts, methods, techniques, theories and models come to the fore with the effect of technology and attract the attention of researchers. One of them is blended learning. Blended learning is a learning process in which both face-to-face learning processes and learning processes in online environments coexist. Today's learners are expected to be able to solve problems, work collaboratively, and have strong communication. It is thought that peer learning can be used in constructivist teaching processes in order to gain these features. Peer learning involves learners performing their learning by interacting with each other. In this study, it is aimed to determine the opinions of teacher candidates about peer learning realized with interactive videos in the blended learning process. The study group consists of 37 Computer and Instructional Technologies Education Department teacher candidates, 11 women (29.73%) and 26 men (70.27%) enrolled in the "Special Teaching Methods - II" course in the spring semester of 2018-2019 academic year. In the online part of the study, a web 2.0 tool (Edpuzzle) was used to prepare interactive video content. The videos prepared by the peers regarding the course content were expected to be watched online and before the face-to-face lessons. In the face-to-face learning process, students progressed the learning process interactively with their peers. At the end of the process, the data were collected with the data collection tool named "teacher candidate opinion form" developed by the researchers from the study group. The collected data were analyzed with content analysis and interpreted by the researchers. In the study results, the opinions of the teacher candidates about the process after their learning experiences were determined. It was found that a great majority of the teacher candidates had a positive opinion about the peer learning realized with interactive videos in the blended learning process.
KerkoCite.ItemAlsoKnownAs: 10.31014/aior.1993.04.02.281 2339240:QFNTPDR9 2405685:4CPCU8MQ

China: testing a decade of online education preparation - Liangdi, Xu; Groenewegen-Lau, Jeroen (EdTech Hub, 2020)
ZenodoArchiveID: 4705990 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705990 2339240:S2B995E4 2405685:P5B4YWID
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Measuring Effectiveness of Mobile Application in Learning Basic Mathematical Concepts Using Sign Language - Parvez, Komal; Khan, Muzafar; Iqbal, Javed; Tahir, Muhammad; Alghamdi, Ahmed; Alqarni, Mohammed; Alzaidi, Amer Awad; Javaid, Nadeem (2019)
Technology plays an important role in our society, especially in the ﬁeld of education. It is quite regrettable that people, particularly the deaf, still face a lot of challenges in acquiring an education. Their learning methods are different as compared to hearing people. They use Sign Language (SL) rather than natural language to communicate and learn. They are required to put a lot of effort into learning different concepts using conventional pedagogies. Therefore, there is a dire need for some assistive technology to improve their learn-ability and understandability. In the present study, 192 deaf participants aged 5–10 years were sampled from two special child institutes. The objective of the present study was to determine the effectiveness of a mobile interface through a developed mobile application for learning basic mathematical concepts using Pakistan Sign Language (PSL). The present study bridges the gap between the technology-based method and conventional teaching methods, which are used for teaching mathematical concepts using PSL. The participants were divided into two groups, that is, one group learned through conventional methods (ﬂash cards and board) and the other group through the developed mobile application. The difference in the performance of both the groups was evaluated by conducting quizzes. The quiz results were analyzed by the Z-test and ANOVA. The ﬁndings revealed that the Experimental Group (EG) participants, who were instructed by our mobile application showed higher proﬁciency in the quizzes as compared to the Control Group (CG). EG participants performed better than CG by 12% in the quizzes. A gender based difference was also observed for the quiz scores. Male participants in category C (word problem learning) performed 2.7% better than females in the EG and 2.5% better in the CG. Moreover, a signiﬁcant difference was also observed in the time taken by participants in both groups to complete the quizzes. CG participants took 20 min longer than EG participants to complete the quizzes. The results of the ANOVA showed that the quiz scores were directly affected by the mode of teaching used for participants in both groups.
KerkoCite.ItemAlsoKnownAs: 10.3390/su11113064 2339240:PJGV4NQP 2405685:A5XR2HFD

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:WMMVHIHD 2405685:ERPJWFQ4

Guidance on Facilitation of E-Learning - Dzinotyiweyi, Monica; Chuang, Rachel; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396251 10.53832/edtechhub.0087 2405685:CMEQA5F7
Keywords: F: Helpdesk response; _r:AddedByZotZen

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.
KerkoCite.ItemAlsoKnownAs: 2339240:J83HRBE6 2405685:BTDXQFJ9

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

"Let's not leave this problem": exploring inclusive education in rural South Africa - Mitchell, Claudia; De Lange, Naydene; Thuy, Nguyen-Thi Xuan (Prospects: Quarterly Review of Comparative Education, 2008)
Inclusive education represents a new agenda for educational reform that spans a wide range of socio-political, cultural, ethical, personal and interpersonal dimensions. Working towards educational inclusion demands commitments, responsibilities and initiatives on the part of all parties to take into consideration the meanings and purpose of education and social justice, to engage and take collective actions in their struggle to combat the diverse forms of educational and social exclusion. This paper presents an educational initiative to implement inclusive education in rural KwaZulu-Natal, an area of South Africa that is most seriously affected by the pandemic of HIV and AIDS. Through the implementation of participatory video-making projects in two schools, the authors seek to empower the voices and actions of teachers in an effort to cope with the problems of poverty and marginalization facing many children. The outcomes of this type of participatory work with teachers have implications for the policy-making process, which in turn, could change the ways educational policy research is structured and implemented.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/61950460?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-008-9057-y 2339240:BV8QZH7J 2405685:G5SZS5H6 2405685:X66PVJWQ 2534378:RJ6ZCAD4 2534378:TTCJ2RZE 2534378:WG3HWTSN
Keywords: Access to Education; Acquired Immunodeficiency Syndrome (AIDS); Developing Nations; Disabilities; ERIC; Current Index to Journals in Education (CIJE); Education; Education reform; Educational Change; Educational Policy; Foreign Countries; Human immunodeficiency virus–HIV; Inclusive Schools; Mainstreaming; Multicultural education; Policymakers; Poverty; Researchers; Rural Areas; Rural areas; Social Attitudes; Social Bias; Social Isolation; Social Justice; Social activism; South Africa; Special Needs Students; Teacher Attitudes; __:import:01; __:match:final; __:matched; __:study_id:2098725; __finaldtb

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

Investing in Science, Technology, Engineering and Math (STEM) Education to Build Africa’s Resilience Against Climate Change - United Nations (United Nations Office of the Special Adviser on Africa, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:CYYBCDFF 2405685:XWIPV7D3

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Improving teaching and learning mathematics in Malawi primary schools: a review of reforms, interventions, successes and challenges - Kazima, Mercy; Longwe, Justina; Gobede, Fraser (Journal of Applied Learning & Teaching, 2022)
KerkoCite.ItemAlsoKnownAs: 10.37074/jalt.2022.5.S2.3 2339240:4FKUR5CB 2405685:EDYLSVNI

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651932 previousDOI: 10.5281/zenodo.4917221 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4917221 10.5281/zenodo.5651932 2405685:V6UCUGBZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Universal Design for Learning: Theory and Practice - Meyer, A; Rose, D; Gordon, D (Center for Applied Special Technology., 2016)
KerkoCite.ItemAlsoKnownAs: 2339240:E35ITZ2D 2405685:ZR5RX227

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Use of Information communication technology in teaching and learning processes in secondary schools in Rachuonyo South District, Homa-Bay County, Kenya - Obonyo, Samson O. (University of Nairobi, 2013)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in teaching and Learning in Rachuonyo South District secondary schools. The focus was on three main subject matters: on ICT use and competence, on teacher and student and on ICT infrastructure and teaching practices. The study is closely connected to the national educational policy, which has aimed strongly at supporting the implementation of ICT in pedagogical practices at all institutional levels. Six research questions were formulated to guide the researcher investigate the phenomena. A descriptive survey design was used to collect data from the field through the use of questionnaire and an observation schedule. The result indicated that ICT has not been successfully integrated in teaching and learning in schools. In general, students are capable and motivated users of computers. Some students have the skills to use new kinds of applications and their ICT skills are wider although not necessarily adequate. Teachers’ skills are more heterogeneous. The large majority of teachers have sufficient skills for everyday and routine working practices, but many of them still have difficulties in finding a meaningful integration of ICT into teaching and learning. Most teachers reported that the use of ICT in learning and teaching was slow in the past years and proposed upgrading of students computer labs and accelerating internet connectivity in the schools. Further, teachers’ good ICT competence helps them to adopt new pedagogical practices and integrate ICT in a meaningful way. The results also showed that students are capable and motivated users of new technology and their ICT skills are wide, although not necessarily adequate; the working habit might be ineffective and wrong. Some students have a special kind of ICT related adaptive expertise, which develops in a beneficial interaction between students and teachers, and individual interest and activity. The most common goal to student use of ICT is challenged by the internet, digital communication and the need to filter information. Since students’ ICT skills can be translated to increased creativity, which include innovation and productive workforce, to develop capacity to ICT which support the country’s knowledge base. The findings further indicated that ICT integration realized some challenges such as availability of sufficient number of ICT tools, lack of motivation and support and lack of technical support. The challenges are either teacher-level (Microlevel), school level (Meso-level) or system level (Macro-level). These barriers have hindered successful implementation of ICT into teaching and learning processes. The study also recommended that teachers should be given sufficient training on how to use ICT tools to enhance teaching and learning in schools. The study also recommended that students should be equipped with ICT skills such as Microsoft software applications such as word, excel and access. Finally, further research on the perception of teachers and students towards the use of ICT in enhancing teaching and learning and relevant strategies for using ICT to improve teaching and learning practices should be conducted.
Accepted: 2013-09-13T12:53:42Z KerkoCite.ItemAlsoKnownAs: 2339240:VMGJH5RH 2405685:K3FR5Q2D

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FY4BHGH3

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7314047 ZenodoArchiveConcept: 7314046 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7314047 10.53832/edtechhub.0152 10.53832/edtechhub.1024 2405685:99ZRGDBB 2405685:NMJMENAG
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

“Why is it speaking to me?”: Refugee-background students’ experiences of education - Câmara, Jáfia Naftali (NORRAG, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QT8TJHMU 2405685:Y8D7AMRR

Entry, engagement and empowerment: Dilemmas for inclusive education in an Indian context. - Singal, N; Florian, L (The Sage Handbook of Special Education, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:6ZNPUAW5 2405685:BQE39QTV

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6981598 ZenodoArchiveConcept: 6981597 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6981598 10.53832/edtechhub.0105 2405685:BDT76583
Keywords: _r:AddedByZotZen

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Impact of technology integration on education in emergency (EiE): An analysis of emergency remote education at K-12 level for girls in Afghanistan since 2020 - Ahmadi, Sima (Research Highlights in Technology and Teacher Education Special Edition, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:TTJ8NHX2 2405685:WNXNUQ2D

Instructional and assessment accommodations in the 21st century. - Thurlow, M (The SAGE Handbook of Special Education: Two Volume Set., 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:HHLQ7XS4 2405685:QCATQYFU

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.
KerkoCite.ItemAlsoKnownAs: 2339240:MMWPL7JY 2405685:NEXA5KQM

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Remote Learning: Rapid Evidence Assessment - Education Endowment Foundation (Education Endowment Foundation, 2020)
This rapid evidence assessment aimed to investigate methods that schools could use to support remote learning during school closures caused by the 2020 coronavirus pandemic (Covid-19). The review sought to find the best evidence behind the wide array of approaches that schools might choose to use during the crisis. The review systematically searched for/through existing meta-analyses and systematic reviews to find the best evidence for a wide range of approaches. In addition to the direct teaching of pupils online by teachers, the review also found evidence for approaches that pupils can use independently, including with technology that adapts the content of tasks in order to provide additional challenge or support, educational games, and for approaches that support peer interaction. The review also examined blended learning approaches, which combine remote and classroom teaching. While these approaches may not be directly applicable during school closures, they were included in case there were useful lessons to be learned that were relevant to the current context of home learning. This report summarises the findings from 60 systematic reviews and meta-analyses answers under five key topic areas: - General remote teaching and learning - Blended learning - Computer-supported collaborative learning - Computer assisted instruction - Educational games Another crucial aspect of supporting pupil’s learning is parental engagement. Parental engagement approaches are beyond the scope of this review, but an existing EEF guidance report, Working with Parents to Support Children’s Learning (2019), and accompanying evidence review summarise the best available evidence for engaging parents in their children’s education. In each section, we have detailed the included reviews and listed Findings and implications drawn from the evidence. We have also highlighted case studies from projects funded by the Education Endowment Foundation in which similar approaches have been rigorously evaluated in English schools.
ZenodoArchiveID: 4477023 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4477023 2259720:VZ7YJUFN 2339240:85V26WNW 2339240:HGMUANP7 2339240:JIW4TDS5 2339240:VJ8WRVRV 2405685:8ASGAE9Q 2405685:B3K7PU24 2405685:GPMMTF99 2405685:HCC97T3B 2405685:LW2NDPNQ 2405685:V3SZZR28
Keywords: Methods; _DOILIVE; _EdTechHub_Output; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Online and distance teaching and learning A32ARSFK; _cover:other:ok; _zenodo:submitted; _zenodoETH

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803101 10.53832/edtechhub.0077 2405685:VFV5SG9H
Keywords: _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
previousshortDOI: 10/ghgngk previousshortDOI: 10/ghgngk previousDOI: 10.5281/zenodo.3631750 previousshortDOI: 10/ghgngk EdTechHub.Copy: 2129771:5EWDQDIA EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngk KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631750 10.53832/edtechhub.0013 10/ghgngk 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:978RP7D4 2405685:VM6NXYF3
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14172051 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1069 ZenodoArchiveConcept: 14172050
Keywords: _r:AddedByMyEducationEvidence

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

What-are-countries-that-already-use-remote-learning-doing-and-what-can-we-learn-from-them-EdTechHub.pdf
KerkoCite.ItemAlsoKnownAs: 2405685:NLH4548E

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

What does the research suggest is best practice in pedagogy for remote teaching? - McAleavy, Tony; Gorgen, Kristine (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:89I7MWHD 2405685:XHIZKSIA
Keywords: ___working_potential_duplicate; ⛔ No DOI found

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
ZenodoArchiveID: 7139243 ZenodoArchiveConcept: 7139242 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7139243 10.53832/edtechhub.0122 2405685:Z8B66R9X
Keywords: _r:AddedByZotZen

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

الامتحانات عبر الإنترنت في سياقات الطوارئ: هل المراقبة، والتقنيات الأخرى، مجدية في سوريا لتيسير عقد امتحانات تشمل جميع الطلاب؟ - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; AlMekdad, Bayan; Sabboura, Rani; Sheqem, Yazeed (EdTech Hub, 2022)
كلمات مفتاحية: الامتحانات عبر الإنترنت، تكنولوجيا مراقبة الامتحانات، سياقات الطوارئ، سوريا خلاصة: الغرض من هذه الوثيقة تقديم دليل يمكن استخدامه من قبل الممارسين في مجال التعليم العاملين في سياقات الطوارئ لتقييم مدى جدوى تنفيذ الامتحانات الإلكترونية واستخدام تكنولوجيا مراقبة الامتحانات. سيتطلب عقد الامتحانات عالية المخاطر عبر الإنترنت في سوريا وفي سياقات طوارئ أخرى استثمارات كبيرة لتحقيق المتطلبات الأساسية اللازمة للجدوى والمصداقية. تشمل هذه المتطلبات الأساسية الكهرباء والإنترنت والأجهزة، بالإضافة إلى تطوير المهارات الرقمية اللازمة للطلاب لتقديم الامتحانات عبر الإنترنت وللمعلمين والإداريين لتيسير الامتحانات عبر الإنترنت. ينبغي بذل المزيد من الجهود لمنع تسريب المعلومات حول الأسئلة ومحتوى الامتحانات، ولتشجيع التغيير الثقافي حول الامتحانات عبر الإنترنت. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7143871 ZenodoArchiveConcept: 7143870 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7143871 10.53832/edtechhub.0124 2405685:9DZXFIC7
Keywords: _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Videos as a Tool in Teacher Professional Learning: How Do Videos Scaffold Teachers’ Understanding of the Behaviours of Students with ASD? - Lam, Cici Sze-ching (Promoting Collaborative Learning Cultures to Help Teachers Support Students with Autism Spectrum Disorder, 2022)
Videos are often used in teacher training. However, when considering professional learning for teachers in supporting students with autism spectrum disorder (ASD), the manner by which teacher educators can make use of videos in professional learning has rarely been documented. On the basis of a model called ‘Fostering a Community of Learners’ (FCL), this chapter aims to show a case study on how a professional learning course for in-service teachers uses videos as a tool to train teachers in understanding pedagogies and handling students with ASD, thus providing a platform for teachers to discuss their common points of interest. Individual interviews were conducted to understand the process of video learning. Hopefully, this article will inform practitioners or teacher educators on the use of videos and case studies in assisting teachers to understand the needs of students with ASD. Implications focus on how scaffolding of knowledge of the behaviours of students was supported with the use of videos in an FCL cycle.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-16-6417-5_12 2339240:4LM2MG4W 2405685:C62C3XAQ
Keywords: Scaffolding; Teaching self-efficacy; Video learning

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PX8LX2HD 2405685:HWT67YS2 2405685:MUSAVHQ9

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7306712 ZenodoArchiveConcept: 7306711 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7306712 10.53832/edtechhub.0132 2405685:ACLTCQV2 2405685:XIIQ4FSE
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Overview of emerging country-level response to providing educational continuity under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7510031 ZenodoArchiveConcept: 7510030 KerkoCite.ItemAlsoKnownAs: 2129771:K9HHIYYP 10.5281/zenodo.7510031 10.53832/edtechhub.0156 2405685:B8SQMMBA
Keywords: _r:AddedByZotZen

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen